جوانب من العلاقات السياسية بين الدولة الرستمية في تيهرت والدولة الأموية في قرطبة - الفيلالي, عبد العزيز (الكراسات التونسية, 1991)
اقتصرت المباحث التي خاضت في شبكة الطرقات بين جزيرة جربة والمجال القاري إما على دراسة طريق القنطرة الذي شيد منذ الفترة الرومانية أو المسلك البحري الذي يفصل أجيم على مضيق الجرف. نحاول في هذا المقال رفع الالتباس والخلط الذي سقطت فيه دراسات عديدة، عربية وغربية على السواء، بين الطريقين البريين "القنطرة" و"الجمال" اللذان ربطا جزيرة جربة بالمجال القاري من جهة بحيرة بوغرارة الجنوبية. أما المنهج المتبع فهو إعادة قراءة معطيات النصوص المصدرية الكلاسيكية (العربية والأجنبية) ومقارنة معلومات الإخباريين بتلك التي وصلتنا عن طريق الرحالة والبحارة المتوسطيين. هذه المعطيات كفيلة لوحدها بتبين وجود طريقين منفصلين لكل منهما تاريخه ووظيفته

البحرين وعمان في عصر النبوة - المسري, حسين علي (المجلة العربية للعلوم الإنسانية, 1992)
بدأنا هذه الدراسة بالحديث عن الحدود الجغرافية القديمة لكل من البحرين وعمان، ثم تحدثنا عن أولى القبائل العربية التي سكنت هذه المناطق ، فوجدنا أن قبائل الأزد والنزارية سكنت عمان، بينما قبائل عبد القيس وبكر بن وائل وربيعة سكنت البحرين. وعندما ظهر الإسلام بعث رسول الله صلى الله عليه وسلم سفراءه إلى البحرين وعمان في أعقاب الهدنة التي عقدها مع قريش. فبعث العلاء بن عبدالله الحضرمي بكتاب إلى المنذر بن ساوي حاكم البحرين، فآمن المنذر وأهل البحرين بدعوة رسول الله ودخلوا الإسلام، ما عدا اليهود والنصارى وكذلك المجوس، وقد اتفق معهم العلاء على أن يدفعوا الجزية. وظل المنذر حاكما على البحرين نائبا عن رسول الله صلى الله عليه وسلم، بينما العلاء أصبح مسئولا عن الصدقات، فكان يجمعها ويبعث بها إلى المدينة . وقد خرجت الوفود من البحرين لمقابلة رسول الله صلى الله عليه وسلم، ومعظم هذه الوفود كانت من قبيلة عبد القيس، والوفد الأول كان برئاسة المنذر بن عائذ بن المنذر المعروف بالأشج، يتألف من 16 رجلا قابل النبي صلى الله عليه وسلم بالمدينة في السنة الثامنة من الهجرة، أما الوفد الثاني، فكان في السنة التاسعة من الهجرة برئاسة الجارود بن المعلي. أما عمال رسول الله صلى الله عليه وسلم على البحرين ، فهم المنذر بن ساوي، مسئول عن النواحي السياسية، والعلاء بن الحضرمي وأبان بن سعيد بن العاص فكانا مسئولين عن الصدقات. أما عمان، فبعث إليها رسول الله صلى الله عليه وسلم سفيريه، أبا زيد قيس بن سكن، وعمرو بن العاص إلى جيفر وعبد حاكمي عمان، فآمنا ودخلا في الإسلام بعد تردد، وكان جيفر هو الحاكم على عمان نائبا عن رسول الله بينما عمرو بن العاص، فكان مسئولا عن الصدقات ن وأبا زيد قيس بن سكن، فكان مسئولا عن الصلاة، وتعليم الناس الإسلام، وخرجت الوفود من عمان إلى المدينة لمقابلة رسول الله صلى الله عليه وسلم، واستمر جيفر حاكما على عمان حتى بعد وفاة رسول الله صلى الله عليه وسلم.

الصراع على السلطة في سلطنة زنجبار العربية في العقود الأخيرة من القرن التاسع عشر الميلادي - تركي, بنيان سعود (المجلة العربية للعلوم الإنسانية, 1995)
يتصدى هذا البحث لدراسة الصراع الأسري البوسعيدي على السلطة في سلطنة زنجبار العربية في العقود الأخيرة من القرن التاسع عشر الميلادي. وهي محاولة أراد بها الباحث تسليط الضوء على طبيعة، وأسباب النزاع الأسري، ودوافعه، مع تتبع للسياسة البريطانية حياله. وقد قسمت هذه الدراسة إلى مراحل زمنية بحسب تسلسل الحكم في السلطنة العربية، واستهلت بعهد السيد برغش بن سعيد، سلطان زنجبار (1870 – 1888)، وأشارت بنبذة مختصرة إلى محاولته الاستيلاء على السلطة في عهد شقيقه السيد ماجد، ودور الحكومة البريطانية في نفيه ثم إعادته إلى زنجبار ، وتحليل الأسباب التي حدت بالحكومة البريطانية إلى توليته الحكم، والذرائع التي ساقتها لرفض طلبه تعيين ابنه وريثا على عرش السلطنة العربية. استعرضت الدراسة بعد ذلك ظروف تعيين السيد خليفة بن سعيد على مقاليد السلطة في زنجبار (1888-1890) وبينت علاقته المتوترة بالقناصل الأجانب، وعلى وجه الخصوص القنصل البريطاني، وأبرزت استغلال الأخير لشقيق السلطان السيد علي، والمتنفذين العرب للمطالبة بعزله ، مما ترتب عليه رضوخ السلطان، وقبوله الأمر الواقع حفاظا على حكمه. كما ألفت الدراسة الضوء على تولي السيد علي بن سعيد حكم السلطنة العربية (1890-1893)، وموافقته على إخضاع زنجبار للحماية البريطانية، وإقدامه على العديد من التنازلات المالية والإدارية ثمنا للبقاء على كرسي الحكم، ثم أشارت إلى تدهور حالته الصحية واستعرضت أبرز المطالبين بولاية الحكم، وموقف الحكومة البريطانية من كل منهم، مع دراسة، وتحليل الشروط البريطانية الجديدة التي وضعها القنصل البريطاني بروتال لتولي السلطنة. كما تناولت محاولة الأمير خالد بن برغش الاستيلاء على السلطة، وأسباب فشلها، وما تلا ذلك من تعيين حمد بن ثويني سلطانا على زنجبار، وخلصت الدراسة إلى أن الحكومة البريطانية استغلت مسألة وراثة الحكم بين أبناء وأحفاد السيد سعيد كسيف مصلت، ونظرت إليها على أنها من الأمور التي يجب ألا يبت فيها دون موافقتها. وهكذا نجحت في إشعار المعنيين من سلاطين زنجبار بأنهم إنما يحكمون عن طريق الهيمنة ، والنفوذ البريطاني لا عن طريق الشعب ، واختياره.

ثورات أهالي إقليم جعلان ضد سلطة حكومة مسقط في القرن التاسع عشر (باللغة الإنجليزية) - آل عمر, سعيد بن عمر (مجلة دراسات الخليج والجزيرة العربية, 1997)
يناقش هذا البحث بالدراسة والتحليل موقف أهالي إقليم جعلان من حكومة مسقط في القرن التاسع عشر وقد ركز على دراسة الأوضاع الاجتماعية لسكان هذا الإقليم بعمان والظروف التي جعلت القبائل تتخذ موقفا غير ودي من حكومة مسقط في القرن التاسع عشر . وقد ناقش البحث في استعراض سريع أهم القبائل التي تسكن الإقليم وفي مقدمتها قبيلة بني بوعلي والظروف السياسية والدينية التي كانت سائدة فيه وكيفية قبول أبناء هذا الإقليم للفكر السلفي وتأثرهم بالدعوة السلفية في نجد من خلال تأثر أحد أبناء الأسر المتزعمة لإحدى القبائل المهمة هناك بدعوة الشيخ محمد بن عبدالوهاب ثم أثر هذا بدوره في أبناء عشيرته وقادها إلى هذا التوجه ، مما ترتب عليه اتخاذ أبناء هذا الإقليم لذلك الموقف غير الودي والعصيان على حكومة مسقط ، خاصة بعد نفوذ الدولة السعودية الأولى الواضح في منطقة عمان خلال العقد الأول والثاني من القرن التاسع عشر ، والذي أدى بالتالي إلى شيء من ولاء أبناء هذا الإقليم الديني والسياسي لولاة الدولة السعودية الأولى وقادتها في واحة البريمـي . وقد أدى هذا الأمر إلى أن يستثمر السيد سعيد بن سلطان حاكم عمان صداقته مع حكومة بومباي البريطانية التي تحالف معها في الحملات العسكرية على القواسم لأن يجر الإنجليز إلى مساعدته للهجوم على هذه القبائل في حملتين مشتركتين عمانية بريطانية بحجة هجومهم على إحدى السفن الإنجليزية وقد نفذت الحملتان على أثر سقوط الدولة السعودية الأولى التي كان هؤلاء يدينون لها بالولاء فكريا وسياسيا . وقد ناقش هذا البحث الظروف التي أرسلت فيها الحملتان والصعاب التي واجهت منفذيهما . لكن ذلك الهجوم وإن نجح في الحملة الثانية في الإساءة إلى أبناء هذا الإقليم وسقوط أعداد منهم بين قتيل وجريح وأسير إلا أنه عمق في نفوسهم الموقف المعادي لحكام مسقط وأصبح هؤلاء يلعبون دورا رئيسيا في أحداث عمان السياسية وفي كل خلاف على الحكم في مسقط بين الأسرة الحاكمة ولهذا استمر العداء بين أبناء هذا الإقليم وسلطات مسقط وكانوا ينضمون إلى من يحترم مشاعرهم الدينية وعقيدتهم السلفية من أسرة آل بوسعيدي الحاكمة في مسقط ويؤيدونه ويخلصون له الولاء والطاعة لاسيما في النصف الثاني من القرن التاسع عشر بعد أن تقلص النفوذ السعودي في المنطقة .

نفوذ الإمام سعود بن عبدالعزيز في عمان وموقف حكومة الهند البريطانية منه 1218 - 1226هـ / 1803 - 1811م. - الجهني, عويضة بن متيريك (مجلة دراسات الخليج والجزيرة العربية, 1998)
نفوذ الإمام سعود بن عبدالعزيز في عمان وموقف حكومة الهند البريطانية منه 1218-1226/1803-1811م . تهدف هذه الدراسة إلى تحقيق أمرين ، الأول منهما هو التوصل إلى حقيقة مدى قوة نفوذ الدولة السعودية في عمان خلال عهد الإمام سعود بن عبدالعزيز ، والثانـي منهما هو محاولة كشف موقف حكومة الهند البريطانية تجاه ذلك النفوذ . قبل الدخول في مناقشة هذين الأمرين تم التمهيد لهذه الدراسة بنبذة مختصرة عن أوضاع عمان ، ومصالح حكومة الهند البريطانية في الخليج العربي ، وامتداد النفوذ السعودي إلى شرق جزيرة العرب مع نهاية القرن الثامن عشر للميلاد . وتنصب المناقشة الرئيسية على جهود الإمام سعود لتقوية النفوذ السعودي في شمال عمان ومسقط منذ ان وصل إلى الحكم في عام 1218هـ/1803م ، وما مدى نجاحه في تحقيق ذلك . كما تحاول الدراسة استكشاف التهديد الذي مثله النفوذ السعودي لمصالح حكومة الهند البريطانية في عمان ، وكيف استجابت تلك الحكومة لذلك التهديد وما مدى نجاحها في ذلك . ختمت الدراسة بوصول الحملة العثمانية المصرية إلى الحجاز في عام 1226هـ/1811م ، لما كان لهذا الحدث من أثر على النفوذ السعودي في عما والموقف البريطاني منه .

التحديث السياسي في عمان: دراسة في أثر التحديث البنيوي على سلطة الحاكم - الدخيل, عبد الكريم حمود (مجلة دراسات الخليج والجزيرة العربية, 1996)
في 23 من يوليو 1995م ، احتفلت عمان بمرور خمسة وعشرين عاما على تولي السلطان قابوس للحكم . وخلال هذه الفترة الوجيزة نفضت عمان عن نفسها ملامح التخلف وشهدت مسيرة من التطور والتحديث شملت العديد من المجالات الاجتماعية والاقتصادية والسياسية . وفي المجال السياسي ، تعود بداية إرهاصات التغير والإصلاحات في بنية النظام الحاكم ، إلى عام 1920م ، وذلك حين أدخلت عدد من الإصلاحات لتنظيم الشئون المالية والإدارية والعسكرية ، ثم استمرت عملية الإصلاحات بطيئة ومتذبذبة خلال العقود اللاحقة وحتى عام 1070م . وعلى الرغم من إدخال بعض الإصلاحات – خاصة على بنية الجهاز التنفيذي – بقي النظام الحاكم في عمان يحمل ملامح التخلف ويعيش في حالة من العزلة الداخلية والخارجية ، دفعت بالسلطان قابوس إلى إزاحة والده وتولي السلطة في 23 من يوليو 1970م . وبوصول السلطان قابوس إلى الحكم ، فضلا عن تضافر مجموعة من الضغوط والعوامل الأخرى – مثل ثورة ظفار وزيادة العائدات النفطية – شهد النظام السياسي مرحلة من التحديث والتطور البنيوي ، ولقد تجسدت عملية التحديث في بروز وتطور – بدرجات متفاوتة – مؤسسات وأجهزة حكومية متعددة تنفيذية وقضائية وتشريعية ، واقتـرن بذلك قدر لا بأس به من التخصص الوظيفي في تقسيم الأعمال والمهام . كما شملت عملية التحديث البنيوي – وبدرجة محدودة – بروز بعض الأبنية التحتية الحديثة . إن عملية التحديث السياسي في هذا السياق البنيوي تحمل آثارا سياسية متعددة الأبعاد من شأنها أن تؤدي إلى تحولات وتبدلات في كيفية ممارسة السلطة السياسية . وذلك لأنها عملية تعيد تنظيم العلاقة بين الهيئات الحكومية وكذلك توزيع الاختصاصات والسلطات ، وقد تخلق أيضا مؤسسات تؤطـر ممارسة الحكم ، وبالتالي فإن عملية التحديث البنيوي في مسيرتها التفاعلية قد تؤدي إلى تقييد سلطة الحاكم الفردية .

التطورات الداخلية في عمان في عهد الإمام أحمد بن سعيد البوسعيدي ( 1700 - 1783). - القحطاني, عبد القادر حمود (مجلة دراسات الخليج والجزيرة العربية, 1999)
تتلخص هذه الدراسة في الآتـي : أولا : الأوضاع الداخلية في عمان قبل ولاية أحمد بن سعيد الإمامة . ثانيا : الغزو الفارسي لعمان 1737-1744م . ثالثا : حياته وأعماله وموقفه من الغزو الفارسي لبلاده (1700-1744م) . رابعا: مبايعة أحمد بن سعيد ، بالإمامة 1744م . خامسا: سياسته الداخلية . سادسا: النشاط التجاري في عهده . لقد استطاعت دولة اليعاربة التي حكمت عمان بين 1624-1744م ، طرد الغزاة البرتغاليين من البلاد ومن الخليج وشرق أفريقيا . كما تعرضت البلاد أيضا في عهد دولة اليعاربة للغزو الفارسي ، في الفترة ما بين 1737-1744م ، ولكن أحمد بن سعيد البوسعيدي ، والي صحار حينذاك تمكن بالتعاون مع الإمام سلطان بن مرشد اليعربي ، والتفاف الناس تحت قيادته من طرد الغزاة نهائيا من البلاد في عام 1744م .مبايعة أحمد بن سعيد بالإمامة سنة 1744م : تعتبر وفاة الإمام سلطان بن مرشد اليعربي في سنة 1744م ، نهاية عصر دولة اليعاربة ، وخاصة أنه حدث عقب وفاته انقسام في داخل أسرة اليعاربة ، مما أتاح ظهور قوى جديدة في البلاد ، هي قوة آل بوسعيدي ممثلة في أحمد بن سعيد البوسعيدي . وقد تم انتخاب أحمد بن سعيد ، لإمامة عمان ، وذلك بسبب الدور البطولي الذي قام به لتحرير بلاده من الفرس . وقد اتخذ الإمام أحمد ، من مدينة الرستاق ، عاصمة لحكمه . وعمل الإمام أحمد ، منذ توليه مقاليد السلطة على توحيد القبائل العمانية تحت حكمه . وأهتم بالتجارة ، والنشاط الاقتصادي ، وبتنظيم أمور الدولة ، حيث أصدر القوانين التي تنظم الشئون الإدارية والمالية ، والقوانين الجمركية . كما أهتم الإمام أحمد ، ببناء القوة العسكرية البرية والبحرية . غير أن سياسته الإصلاحية لم تمنع بعض الطامعين من التمرد على نظام حكمه ومحاولة الوصول إلى الحكم في البلاد ، وكان إبنيه سيف وسلطان ممن خرجا عن طاعته في سنة 1781م . إلا أنه تمكن سن التغلب عليهم جميعا ، وأخضعهم لحكمه . وشهدت التجارة في عهد أحمد بن سعيد ، ازدهارا عظيما نتيجة اهتمامه بميناء مسقط ، والتسهيلات التي كان يقدمها للتجار من العرب والأجانب ، والعمل على حمايتهم وتوفير الأمن والسلامة لهم . وقد ازدهرت التجارة في ميناء مسقط بصورة خاصة بعد تحول النشاط التجاري إليها بعد أن هجر التجار الأوربيون ميناء بندر عباس في سنة 1763م ، على أثر الفوضى السياسية التي اجتاحت فارس حينذاك . وكان يعزز هذا النشاط التجاري ، صناعة السفن في عمان ، واهتمام الحكومة بشراء البعض الآخر من الدول المصنعة . وتذكر بعض المصادر أن دخل حكومة الإمام أحمد ، السنوية من الرسوم الجمركية على البضائع بلغ أكثر من مليون روبية . وقد أثار نجاح الإمام أحمد بن سعيد ، في المجال التجاري ملك فارس كريم خان . الذي هدد بغزو عمان . ولكن بعد أن فشل ملك فارس في إقناع السلطة العثمانية في البصرة ، وكذلك شركة الهند الشرقية الإنجليزية ، بالوقوف إلى جانبه في غزو عمان ، انقلب إلى غزو البصرة في عام 1775م . وقد وقف الإمام أحمد إلى جانب السلطة العثمانية ضد الفرس ، حيث أرسل قوات بحرية في مقدمتها سفينته الحربية (الرحماني) للدفاع عن البصرة . وفي ختام هذه الدراسة ، نستطيع أن نقول ، أن الإمام أحمد بن سعيد البوسعيدي ، المؤسس الأول للدولة البوسعيدية ، قد استطاع إقامة دولته المركزية على أنقاض دولة اليعاربة المنهارة ، على أسس سليمة مبنية على النظام والقانون.
Keywords: Vie politique – Oman – 1624-1742; Vie politique – Oman – 1744-1783

شبكة طرق النقل في منطقة الباطنة بسلطنة عمان: دراسة جغرافية في التحليل الكمي - الطرزي, عبد الله حمادة (مجلة دراسات الخليج والجزيرة العربية, 1999)
يهدف البحث إلى تحليل شبكة الطرق بمنطقة الباطنة بسلطنة عمان وجعلها أكثر فاعلية . وبعد تحليل شبكة الطرق تبينت الحقائق التالية : أولا : بلغ طول طرق الشبكة الكلي 4746 كم2 ، منها 27,1% (1285كم2) معبدة ، والباقي 72,9% (3461 كم2) غير معبدة ، وتتركز المعبدة في المنطقة الساحلية وغير المعبدة في الداخلية .ثانيا : لا توجد طرق معبدة تربط وبشكل مباشر منطقة الباطنة بمنطقتي الظاهرة والداخلية رغم مجاورتها لهما مما جعل العلاقات الاقتصادية الاجتماعية بينها قليلة جدا .ثالثا : بلغ مؤشر الانعطاف عن الخط المستقيم سواء للطرق الرئيسية أو الثانوية 125% ، فهناك 321 كيلومترا زيادة فيما لو سارت الطرق بخطوط مستقيمة .رابعا : وجود نثق وأحيانا غياب كامل للطرق الزراعية في الأدوية الجبلية أمثال : وادي بني عوف ، وادي السحتن ، وادي الصرمي ، ووادي بني هني .خامسا : اختلفت كثافة الطريق بالنسبة لحجم السكان والمساحات بين ولايات المنطقة : فقد سجلت كثافة أعلى في ولايات : صحار ، السويق ، شناص ، بركـاء ، الخابورة ، والعوابي ، وعلى العكس من ذلك في ولايات : الرستاق ، نخل ، صحم ، ووادي المعاول .سادسا : شبكة الطريق حسب مؤشر درجة الارتباط غير مكتملة فهي 83% حسب مؤشر بيتا ، 42% حسب مؤشر جاما ، و8% فقط حسب مؤشر ألفا . من أجل تحسين فاعلية الشبكة توصل الباحث للتوصيات التالية : تعبيد الطرق الرئيسية التي تحمل الأرقام : 8 ، 9 ، 10 ، لربط منطقة الباطنة بالظاهرة . شق طرق رئيسية تربط مدينة الرستاق بكل من مدينة نزوى وعبري . تعبيد مالا يقل عن 1500 كيلومترا من الطرق الزراعية في المناطق الريفية لإنعاش الريف وقراه .

طريق عبر الصحراء الليبية من المغرب الأقصى إلى مصر في القرن السادس / الثاني عشر - موسى, عز الدين عمر (مجلة البحوث التاريخية, 1993)
Keywords: Relations – Djerba – Djebel Nefousa

العلاقات الإقتصادية والثقافية بين الدولة الرستمية وبلدان جنوب الصحراء الكبرى وأثرها في نشر الإسلام هناك - الحريري, إدريس صالح (مجلة البحوث التاريخية, 1993)
Keywords: Relations – Djerba – Djebel Nefousa

نظرات في الفقه الإباضي : رأي يعالج مشكلة لنا حاضرة - حسام الدين, محمد (مجلة الأزهر, 1991)
Keywords: Fiqh

Djerba ; les traditions millénaires et l’histoire des communautés sahariennes - Israël, Herbert (Los Muestros, 1996)
Keywords: Judaïsme – Djerba

L'Arabe du coin et le Chinois du quartier, ou le commerce "ethnique" au service de tous - Barou, Jacques (Hommes et Migrations, 1999)
Depuis ceux que l'on a appelés les "Auvergnats de Paris" jusqu'aux restaurants chinois de nos quartiers en passant par l'épicerie berbère du coin c'est selon un même processus qu'à différentes époques , des migrants d'origines diverses exercent leur activité dans le commerce de proximité, là où le lien familial et communautaire tient une place prépondérante. Ce faisant ces commerces contribuent au maintien de la convivialité dans les espaces urbains.
Keywords: Commerce – Djerba

La mosquée d'Ouni - Ayoub, Abderrahman (Revue des études phéniciennes-puniques et des antiquités libyques, 1990)
Keywords: Ibadisme – Tataouine; Ouni; mosquée (Tataouine; Tunisie)

Brégué et sa mosquée - Ayoub, Abderrahman (Revue des études phéniciennes-puniques et des antiquités libyques, 1997)
Keywords: Braga; mosquée (Tataouine; Tunisie); Ibadisme – Tataouine

Indian Immigrants and the East African Slave Trade - Tominaga, Chizuko (Senri ethnological studies, 1996)
Keywords: Esclavage – Zanzibar

A Stupendous Hammer: Colonial and Post-colonial Reconstructions of Zanzibar's Other Side - Myers, Garth Andrew (Urban Studies, 1995)
Ng'ambo is the historic Other Side of Zanzibar city. The last 50 years have brought two attempts to demolish Ng'ambo and replace it with spaces designed to express the dominance of the state. Differences at first appear to be large between colonial and post-colonial Zanzibar. Yet these reconstructions shared similar objectives, failures and consequences. This paper highlights commonalities between the two projects and ties them to three themes from the literature of colonial cities in Africa concerning colonial urban planning and its post-colonial legacy. These themes include: the bureaucratisation and centralisation of power; the manipulation of space as a means of fostering hegemony; and the alienation of residents from the planning process.
Keywords: Urbanisme – Zanzibar

Intellectual of Empire: Eric Dutton and Hegemony in British Africa - Myers, Garth Andrew (Annals of the Association of American Geographers, 1998)
This essay examines the career of Eric Dutton in five British African colonies from 1919 to 1952, with case studies of his work in Lusaka and Zanzibar. In analyzing Dutton's career, I use a Gramscian conception of the role of intellectuals in creating colonial hegemony, against the backdrop of recent research on the relationship of geography to colonial discourse. Dutton worked and corresponded with key players in Britain's African empire. He was a major force behind early urban-planning programs in East and Central Africa and author of four geographical books. Permanently disabled by war wounds, he was also permanently infatuated with the moral rightness of British imperial culture. A concern for geography's professional relationship with, and the geographical legacy of, colonialism has emerged in recent scholarship on Africa, largely through studies of travel writing, fiction, and nineteenth- or early twentieth-century exploration geography. Later scholar-officials like Dutton sought to apply their knowledge to the shaping of spaces to serve the Empire's direct and immediate needs in Africa, even while trying to win the hearts and minds of its subject peoples. Around Timothy Mitchell's (1988) concept of "enframing," I build an analysis of the spatial projects with which Dutton is most associated and show how Lusaka and Zanzibar were enframed by his plans. Through his publications and correspondences, as well as his seemingly omnipresent service, Dutton has an important legacy that has neither been articulated nor analyzed, one which points to the importance of contextualized biography for analyses of colonial discourse. I argue here for seeing Dutton as an intellectual in the service of colonial hegemony and its enframing spatial discourse, although the character of his agency exemplifies why that attempted hegemony failed.
Keywords: Vie politique – Zanzibar – 1911-1960

Muslim Burial Customs on the East African coast - Juma, Abdurahman (Tor: meddelanden från Uppsala universitets museum för nordiska fornsaker, 1996)
Keywords: Archéologie – Zanzibar

Identity, Difference, and Dance: Female Initiation in Zanzibar, 1890 to 1930 - Fair, Laura (Frontiers: A Journal of Women Studies, 1996)
Keywords: Musique – Zanzibar

Girofle et travailleurs migrants à Zanzibar, 1946-1962 - Crozon, Ariel (Annuaire des pays de l'Océan Indien, 1995)

Une ethnographie dans son contexte : administration coloniale et formation identitaire (Zanzibar) - Bacuez, Pascal (Cahiers d'études africaines, 1998)
Résumé À Zanzibar, l'intervention de l'État colonial tendit à briser la structure des réseaux sociaux basés sur le don rituel, stimula l'émergence de comportements individualistes et se substitua aux dispositifs traditionnels de régulations des échanges. L'article reprend le déroulement de certaines affaires litigieuses concernant le principe de dévolution des biens patrimoniaux dans la société swahili rurale. Une sociologie de l'action coloniale conduit l'auteur à montrer combien l'établissement de rapports de droit conspira finalement, dans le contexte de la société swahili, à mettre en veilleuse des rapports de dons.
Keywords: Vie politique – Zanzibar

The Nineteenth-century Carved Wooden Doors of the East African Coast - Aldrick, Judith (Azania: Archaeological Research in Africa, 1990)
_eprint: https://doi.org/10.1080/00672709009511404
Keywords: Archéologie – Zanzibar

الشيخ احمد بن حمد الخليلي في كتابه ( وسقط القناع ) : عرض ونقد - البسام, أحمد بن عبدالعزيز (الدرعية, 1999)

الإمام جابر بن زيد الأزدي العماني (حياته ومكانته العلمية ) - المشهداني, محمد جاسم حمادي (تاريخ العرب والعالم, 1999)
Number: 182

الصلات التجارية بين عمان و بلاد المغرب في العصر الإسلامي : أسسها ، مظاهرها و نتائجها على البلدين - بوتشيش, إبراهيم القادري (مجلة دراسات تاريخية, 1999)
Number: 069,070
Keywords: Relations – Oman – Afrique du Nord

العلاقات بين اليمن وعمان في العصرين القديم والوسيط - شكري, محمد سعيد (المؤرخ العربي, 1996)
Number: 054
Keywords: Relations – Oman – Yemen

دور الاباضية في نشر الإسلام في بلاد المغرب - خليل, آمال محمد حسن (المؤرخ العربي, 1995)
Number: 052

فتوى رقم 6935 حكم الاسلام من فرق الإباضية وهل يجوز الصلاة خلفهم من الفتوى - السعودية الرئاسة العامة للبحوث العلمية والإفتاء اللجنة الدائمة للبحوث العلمية والإفتاء (مجلة البحوث الإسلامية, 1992)
Keywords: Fatwas – Arabie saoudite – 20e siècle

السياسة الخارجية العمانية من العزلة إلى دبلوماسية الوساطة - نوار, إبراهيم متولي (مجلة السياسة الدولية, 1992)
Number: 110
Keywords: Politique étrangère – Oman – 1970-2020

الشيخ عبدالله السالمي : فقيه ومجاهد - العبيدلي, أحمد (Etudes orientales, 1991)
Number: 009,010

طبنة في مجال العلاقة بين زناتة والفاطميين حى نهاية عهد المنصور الفاطمي - لقبال, موسى (حوليات جامعة الجزائر, 1991)
من بين الميزات الكثيرة لتاريخ المسيرة المذهبية الحمراء، في مغربنا الاسلامي، ميزة اختيار دار الهجرة والقرار، والعصبية الحليفة قبل بدء حركة الدعوة والانتشار. فقد اختار الاباضية بعد اجتهاد، الاجراء الشرقية والوسطى من المغرب الاسلامي، بين البشر، نفوسة ولو اتة وهزاته وزواغة وزناتة، كما اختار الصفربة مضارب مكناسة البترية في صحراء سلجماسة بالمغرب الاقصى. هذا بينما استقر آل الحسن العلويون الزيدية بثقلهم في معاقل الاطلس في مضارب أروبة واحلافها اليرانس. وفي حماية زعيمها أبي ليلى عبد الحميد بن اسحاق الاوروبي ذي الميول الواصلية.

الزخرفة الجصية بين التطور والإنحطاط في المباني الأسلامية بالجزائر ق 4-8 ه - حملاوي, علي (آثار, 1992)
حظيت العمارة الإسلامية بالجزائر إلى الإهتمام الكبير ، فإستخدم القدامى موادة تبدو صلبة كالتراب المدكوك أو الآجر .
Keywords: Architecture – Mzab

المتحف الحديث كيف يجب أن يكون؟ - حملاوي, علي (آثار, 1992)
كثيرا ما تطرق مسامعنا كلمات دون ان نعيرها غهتماما وغالبا ما نرددها بين شفتانا دون فهم معناها، و الامثلة على ذلك عديدة .

La maison d’été du Bachagha de Ghardaïa - Moriaz, Jean (Le Saharien, 1991)
Keywords: Moeurs et coutumes – Mzab

La vraie date d’arrivée des premières autos au M’Zab - Peloux, Guy du (Le Saharien, 1991)

(أهل الله وخاصته) المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 1999)

الرسائل الجامعية (الحياة, 1999)

المنهج الذاكراتي (الحياة, 1999)

بمناسبة وفاة الدكتور صالح الخرفي / 233 (الحياة, 1999)

تحفيظ القرآن بمدرسة الحياة (الحياة, 1999)
Keywords: Enseignement – Mzab

خلاصة عن نظام (الحياة, 1999)

مع الدكتور محمد ناصر بوحجام (الحياة, 1999)

من حصاد المطابع (الحياة, 1999)

الزمن في أدبيات محمد علي دبوز - باباعمي, محمد بن موسى (الحياة, 1999)

(شعر) العيد والثورة - باجو, صالح بن إبراهيم (الحياة, 1999)
Keywords: Poésie – Mzab

(شعر) يا (صالح) الفعال وداعا - باجو, صالح بن إبراهيم (الحياة, 1999)
Keywords: Poésie – Mzab

للأمر بالمعروف والنهي عن المنكر - باجو, مصطفى بن صالح (الحياة, 1999)

الإمام جابر بن زيد، ترجمة حديثية - بازين, عمر بن أحمد (الحياة, 1999)

صور من الإباضية في عهد الموحدين - بحاز, إبراهيم بن بكير (الحياة, 1999)

حياة مع القرآن (2) - حدبون, صالح بن أحمد (الحياة, 1999)

أبو اليقظان: العبقرية والفكر الحضاري - حريزي, موسى بن إبراهيم (الحياة, 1999)

زكاة الأصول الثابتة الاستثمارية - حمدي, محمد بن صالح (الحياة, 1999)
Keywords: Fiqh – Zakāt

الشعر الوطني القومي عند أبي اليقظان - زغينة, محمد (الحياة, 1999)
Keywords: Poésie – Mzab

من مواقف ابن باديس - زغينة, محمد (الحياة, 1999)
Keywords: Réformisme – Mzab

الافتتاحية: معهد الحياة ورسالته - شريفي, سعيد بن بالحاج (الحياة, 1999)

في الفكر الديني الإسلامي - عكاشة, شايف (الحياة, 1999)

البشير الإبراهيمي - فخار, حمو بن عمر (الحياة, 1999)

(شعر) كيف أسلوكِ - لزعل, أحمد موسلمال (الحياة, 1999)
Keywords: Poésie – Mzab

قراءة سَننية في سورة يوسف - لمسن, محمَّد (الحياة, 1999)

الأستاذ بحاز إبراهيم بن بكير ملخص لرسالة دكتوراه - مجاني, بوبة (الحياة, 1999)

دور المرأة في الحركة العلمية بجبل نفوسة - مجاني, بوبة (الحياة, 1999)
Keywords: Vie intellectuelle – Djebel Nefousa

(شعر) آخر العنقود - ناصر, محمد صالح (الحياة, 1999)
Keywords: Poésie – Mzab

موقف الشيخ اطفيش من الاستعمار - وينتن, مصطفى بن الناصر (الحياة, 1999)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914)

المصطلحات الإباضية في كتب السير والتراجم - مزهودي, مسعود (مجلة الحضارة الإسلامية, 1998)
المصطلحات الإباضية في كتب السير والتراجم

İlk Harici Devlet: Rüstemî'ler (60-2971777-909) - Söylemez, Mehmet Mahfuz (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1998)
İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909) İlk Harici Devlet: Rüstemî'ler (60-2971777-909)
Number: 1-4

İbaziyye ve Zeydiyye’de Seferilik Hükümleri - Öz, Mustafa (Seferilik ve Hükümleri, 1997)

Harici Düşüncesinin Gelişimi - Yildiz, Harun (Ondokuz Mayıs Üniversitesi İlahiyat Fakültesi Dergisi, 1999)
Number: 11

Emevi̇ler Dönemi̇ İç Si̇yasi̇ Geli̇şmeleri̇ (41-132/661-750) - Aycan, İrfan (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1999)

سلطنة كلوة الإسلامية تاريخها وحضارتها 975-1515م - العراقي, سر الختم سيد أحمد (بيادر, 1995)

Elisabeth & Robert Darley-Doran, History of Currency in the Sultanate of Oman - Hennequin, Gilles (Revue Numismatique, 1998)
Keywords: Numismatique – Oman; Recension

الرسائل الجامعية (الحياة, 1998)
Keywords: Bibliographie

جابر بن زيد، أبو الشعثاء (الحياة, 1998)
Keywords: Biographies – Oman

قائمة المستظهرين لكتاب الله في مدرسة الحياة (الحياة, 1998)
Keywords: Coran – apprentissage

من حصاد المطابع (الحياة, 1998)

عرض بحوث الحياة3: فضل الصحابة والرضا عنهم (للإمام الشيخ بيوض) - أوجانة, بهون بن يوسف حميد (الحياة, 1998)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

قراءة في كتاب الإباضيّة بين الفرق الإسلاميّة - أوجانة, عبد الوهاب بن محمد حميد (الحياة, 1998)

رسالة الحياة - الخرفي, صالح بن صالح (الحياة, 1998)

عقيدة في معرفة التوحيد والفرائض لأبي سهل - الشريف, مصطفى بن محمد (الحياة, 1998)

البعد التربوي عند الشيخ بيوض - الشيخ بالحاج, عيسى بن محمد (الحياة, 1998)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

الشيخ علي يحي معمّر: باكورة من معهد الحياة - الشيخ بالحاج, قاسم بن أحمد (الحياة, 1998)
Keywords: Biographies – Djebel Nefousa – 20e siècle

دراسات عن الإباضية - النامي, عمرو خليفة (الحياة, 1998)

التجديد في فهم القرآن الكريم عند الشيخ بيوض - بابا عمي, محمد بن موسى (الحياة, 1998)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

عرض بحوث الحياة2: الرسالة الحجَّة - بابزيز, سليمان بن إبراهيم (الحياة, 1998)

قصيدة: صعدت روحه بأقدس بيت - باجو, صالح بن إبراهيم (الحياة, 1998)
Keywords: Poésie – Mzab

منهج الإجتهاد عند الشيخ بيوض - باجو, مصطفى بن صالح (الحياة, 1998)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Ijtihad – Mzab – 20e siècle

الميزابيّون المعتزلة (قراءة جديدة لنصوص قديمة) - بحاز, إبراهيم بن بكير (الحياة, 1998)

المعلم الكفئ يحل كثيرا من مشاكل التعليم - بوحجام, محمد بن قاسم ناصر (الحياة, 1998)
Keywords: Enseignement – Mzab

عرض بحوث الحياة: البدعة؛ مفهومها، وأنواعها، وشروطها (للإمام الشيخ بيوض) - بولرواح, إبراهيم بن علي (الحياة, 1998)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

حياة مع القرآن - حدبون, صالح بن أحمد (الحياة, 1998)

العطل المدرسية في الجزائر - حريزي, موسى بن إبراهيم (الحياة, 1998)

مفهوم الشركة في كتاب القسمة وأصول الأرضين - حمدي, إبراهيم بن محمد (الحياة, 1998)

قصيدة: قال الشهيد - خباشه, صالح بن بابه (الحياة, 1998)
Keywords: Poésie – Mzab

قصيدة: إعتراف الجميل - دواق, سليمان بن عمر (الحياة, 1998)
Keywords: Poésie – Mzab

من أرشيف الحياة - شريفي, سعيد بن بالحاج (الحياة, 1998)

قصيدة: وإسلاماه - عبود, إسماعيل بن محود (الحياة, 1998)
Keywords: Poésie – Mzab

جمعيّة التراث ومشروعها الطّموح لحماية المخطوطات - عوفي, عبد الكريم (الحياة, 1998)
Keywords: Manuscrits – Mzab

الإفتتاحية: مرحبا بالتاريخ يعيد نفسه - فخار, حمو بن عمر (الحياة, 1998)

القيم الإسلاميّة في نظام التعليم بوادي ميزاب - ناصر, محمد صالح (الحياة, 1998)
Keywords: Enseignement – Mzab

Djerba, Ethiopie : La piste africaine - Roten, Hervé (Yuval, 1993)
Keywords: Judaïsme – Djerba

Djerba 1994, souvenirs de mission - Adler, Israel (Yuval, 1994)
Keywords: Judaïsme – Djerba

Le Sahara dans le développement des États maghrébins. I - Bisson, Jean (Maghreb-Machrek, 1991)
L’auteur, qui suit de très près l’évolution du Sahara maghrébin depuis 30 ans, cherche ici à combattre quelques idées reçues, celles d’un Sahara en voie de désertification, d’abandon et de dépeuplement tel que le présentent les nostalgiques de l’agriculture oasienne traditionnelle et du grand nomadisme. Pour lui, la région est, au contraire en pleine transformation et les sociétés sahariennes font preuve d’un grand dynamisme interne : de nouvelles formes d’urbanisation, d’emploi, d’agriculture et d’organisation économique font peu à peu sortir le Sahara de son isolement et offrent des perspectives encourageantes si les contraintes d’un environnement fragile sont respectées. Vu l’ampleur du sujet, seule la première partie de l’étude est publiée dans ce numéro ; la seconde paraîtra dans le numéro 135.
Place: Paris
Keywords: Urbanisme – Mzab

Étude phytogéographique de Djerba et de la Djeffara - Coque, Roger (Annales de Géographie, 1990)
Keywords: Recension

صلابة موقف خليفة بن عسكر من خلال رسالة الى النقيب باري قائد حامية هبية التونسية - مدلل, أحمد عطية (مجلة الوثائق والمخطوطات, 1990)
Keywords: Invasion italienne – Libye

رسائل سليمان الباروني - جبران, محمد مسعود (مجلة الوثائق والمخطوطات, 1991)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

وثائق عن تحركات سليمان الباروني الدولية - الشقروني, توفيق عياد (مجلة الوثائق والمخطوطات, 1991)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

وثائق المغاربة في الاسكندرية في القرن التاسع عشر - عبد الرحيم, عبد الرحيم عبد الرحمن (Revue d'Histoire Maghrébine, 1998)
Keywords: Emigration – Djerba – Egypte

اباضیه و تاریخنگاری - پاکتچی, احمد (مقالات و بررسیها (منتشر نمی شود), 1997)
یکی از فرق اسلامی که در حیات هزار و سیصد ساله خود اهتمامی ویژه به تاریخنگاری مبذول داشته فرقه اباضیه است که در تحقیقات اسلام شناسی ، این بعد از حیات فرهنگی آنان کمتر مورد مطالعه قرار گرفته است. آثار اباضی نه تنها در مطالعه تاریخ این فرقه اساسی ترین منابع محسوب می گردند ، بلکه در مطالعات عمومی تاریخ اسلام در نواحی شبه جزیره و عراق در مشرق ، بخش هایی از شمال و شرق آفریقا در مغرب ، و حتی برخی نواحی ایران چون خراسان و جزایر خلیج فارس منابعی مهم و درخور نیازمند مجالی گسترده است، در این مقاله سعی بر آن بوده تا روشی مبتنی بر دوره های تاریخی و سبک نگارش برای طبقه بندی آثار تاریخی باضیه و معرفی منطقی آنها عرضه گردد. در این مقاله به نوشته ای اباضیان مشرق بیشتر عنایت شده است.
Keywords: Ibadisme – Histoire

Grammaire fonctionnelle de l'arabe du Coran - Hoyos-Andrade, Rafael Eugenio (ALFA: Revista de Linguística, 1991)
Keywords: Recension

Review of Mobile Pastoralists: Development Planning and Social Change in Oman - Lancaster, William (Nomadic Peoples, 1996)
Keywords: Recension

Review of The Sultanate of Oman: A Twentieth Century History - Rigsbee II, W. Lynn (Middle East Studies Association Bulletin, 1996)
Keywords: Recension

Review of Oman: Political Development in a Changing World - Rigsbee II, W. Lynn (Middle East Journal, 1999)
Keywords: Recension

Review of Trade and Empire in Muscat and Zanzibar: Roots of British Domination - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 1993)
Keywords: Recension

Review of The History and Conservation of Zanzibar Stone Town - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 1997)
Keywords: Recension

Review of Socotra: Island of Tranquillity - Bidwell, Robin (British Journal of Middle Eastern Studies, 1992)
Keywords: Recension

Pouwels (Randall L.) : Horn and Crescent. Cultural Change and traditional Islam on the East African Coast 800-1900 - Prunier, Gérard (Outre-Mers. Revue d'histoire, 1990)
Keywords: Recension

Review of Mawsu'at al-Sultan Qabus li-Asma' al-'Arab = Sultan Qaboos Encyclopedia of Arab Names - Auchterlonie, Paul (British Journal of Middle Eastern Studies, 1993)
Keywords: Recension

Review of Mobile Pastoralists: Development Planning and Social Change in Oman - Al-Rasheed, Madawi (The Journal of the Royal Anthropological Institute, 1999)
Keywords: Recension

Review of Oman: Political Development in a Changing World - Joyce, Miriam (International Journal of Middle East Studies, 1999)
Keywords: Recension

Review of Oman: Political Development in a Changing World - Chatty, Dawn (Middle East Studies Association Bulletin, 1998)
Keywords: Recension

Review of The Heritage of Oman; A Celebration in Photographs - McBeath, Neil (British Journal of Middle Eastern Studies, 1998)
Keywords: Recension

Review of Oman and the South Eastern Shore of Arabia - Yapp, M. E. (Bulletin of the School of Oriental and African Studies, 1998)
Keywords: Recension

Review of Mobile Pastoralists: Development Planning and Social Change in Oman - Joyce, Miriam (Middle East Journal, 1997)
Keywords: Recension

Review of Oil and the Transformation of Oman 1970-1995 - McBeath, Neil (British Journal of Middle Eastern Studies, 1997)
Keywords: Recension

Review of Oman and the World: The Emergence of an Independent Foreign Policy - Tétreault, Mary Ann (Middle East Studies Association Bulletin, 1996)
Keywords: Recension

Review of An Early Islamic Family From Oman: al-'Awtabī's Account of the Muhallabids, Journal of Semitic Studies, monograph n. 17; Qasr Ibrīm in the Ottoman Period: Turkish and Further Arabic Documents, «Texts from Excavations» vol. 1, M. Hinds - Salati, Marco (Rivista degli studi orientali, 1995)
Keywords: Recension

Oman: Traditional Arts of the Sultanate of Oman - Stock, Jonathan (The Musical Times, 1993)
Keywords: Recension

Review of History of Currency in the Sultanate of Oman - Bacharach, Jere L. (Middle East Studies Association Bulletin, 1992)
Keywords: Recension

Review of An Early Islamic Family from Oman: Al-'Awtabi's Account of the Muhallabids - Kennedy, Hugh (British Journal of Middle Eastern Studies, 1992)
Keywords: Recension

John Wilkinson. Arabia's Frontiers - Coutan-Bégarie, Hervé (Politique étrangère, 1992)
Keywords: Recension

Ibn Sallām al-Ibâdî (3rd/9th cent.), Kitâb. Published as R. W. Schwartz ansd Sâlim b. Ya'qûb (eds.à, al-Islâm wa ta'rîkhuhu min wujhat nazar ibâdiyya : Beirut: Dâr Iqra', 1405/1985. 182 p. - Donner, Fred M. (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 1992)
Keywords: Recension

Review of The Sultanate of Oman: A Twentieth Century History - Allen, Jr, Calvin H. (Middle East Journal, 1996)
Keywords: Recension

Review of Oman and the World: The Emergence of an Independent Foreign Policy - Allen, Jr, Calvin H. (Middle East Journal, 1996)
Keywords: Recension

Review of Oman: Politics and Development - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 1994)
Keywords: Recension

Review of Mobile Pastoralists: Development, Planning and Social Change in Oman - Allen, Jr, Calvin H. (Middle East Studies Association Bulletin, 1997)
Keywords: Recension

Review of Arabia's Frontiers: The Story of Britain's Boundary Drawing in the Desert - Wrampelmeier, Brooks (International Journal of Middle East Studies, 1993)
Keywords: Recension

Review of Oman - Pridham, B. R. (British Journal of Middle Eastern Studies, 1996)
Keywords: Recension

Review of The Sultanate of Oman: A Twentieth-Century History. - Porter, Brian (International Affairs, 1997)
Keywords: Recension

Review of Oman: Politics and Development. - Porter, Brian (International Affairs, 1993)
Keywords: Recension

Review of An Arabian Princess between Two Worlds: Memoirs, Letters Home, Sequels to the Memoirs, Syrian Customs and Usages - O'Mahony, Anthony (Bulletin of the School of Oriental and African Studies, 1996)
Keywords: Recension

Review of Oman and the World: The Emergency of an Independent Foreign Policy. - Rathmell, Andrew (International Affairs, 1996)
Keywords: Recension

Not Without My Veil: Women in Oman [Oman] 1993 30 min. VHS. Prod: Mia Grondahl for SVT2, Malmo. - Bamia, Aida A. (Middle East Studies Association Bulletin, 1995)
Keywords: Recension

الصراع على زعامة التحزب الهنائي في ساحل عمان من خلال أحداث عام 1845م في ضوء الوثائق البريطانية - العيدروس, محمد حسن (دراسات تاريخية, 1997)
Keywords: Vie politique – Oman – 1804-1856

دولة اليعاربة في الوثائق الهولندية - عبدالله, محمد مرسي (المؤرخ العربي, 1994)
Keywords: Archives – Pays-bas

ابن رزيق المؤرخ العماني - عبد الله, محمد مرسي (المؤرخ العربي, 1996)
Keywords: Oman – Histoire

ابن رزيق المؤرخ العماني - عبد الله, محمد مرسي (التاريخ العربي, 1998)
Keywords: Oman – Histoire

Djerba, un pèlerinage juif aux portes de Marseille - Bitton, Michèle (Provence Historique, 1995)
Keywords: Judaïsme – Djerba

Washington and Treaty-Making with the Sultan of Muscat and Oman - Joyce, Miriam (Middle Eastern Studies, 1994)
Keywords: Relations – Oman – Etats-Unis

جمعية التراث بالقرارة و مشروعها الطموح لحماية المخطوطات في منطقة وادي ميزاب (الجزائر) : القسم الأول - عوفي, عبد الكريم (عالم المخطوطات والنوادر, 1999)
Keywords: Manuscrits – Mzab

جهود الجزائر في فهرسة المخطوطات العربية منذ منتصف القرن التاسع عشر حتى نهاية القرن العشرين - عوفي, عبد الكريم (عالم المخطوطات والنوادر, 1999)
Keywords: Bibliothèques – Mzab; Catalogue – Mzab; Manuscrits – Mzab

العلاقات بين عمان و زنجبار 1277 - 1308 هـ / 1861 - 1891 م - السديس, عبدالرحمن بن علي بن عبدالله (الدارة, 1999)
Keywords: Relations – Oman – Zanzibar

Au M'Zab, vision d'artiste - Bouviolle, Maurice (Mémoire plurielle, 1996)
Keywords: Arts – Mzab

Le sultanat d'Oman - Vital (Bulletin de la Société de géographie de Toulouse, 1997)
Keywords: Récits de voyage – Oman

Omani balancing: Oman Confronts an Uncertain Future - O'Reilly, Marc J. (Middle East Journal, 1998)

Le Sultanat d'Oman: tradition et modernisme - Bausset, Philippe de (Version originale : le trimestriel de réflexion, 1993)

Le Sultanat d'Oman - Kemoularia, Claude de (Version originale: le trimestriel de réflexion, 1993)

Interview with Sultan Qaboos Bin Said Al Said - Joyce, Anne; Al Said, Qaboos bin Said (Middle East Policy, 1995)
This interview with the head of state of the Sultanate of Oman was conducted in writing during the last week in January 1995 by Anne Joyce, editor of Middle East Policy.
Keywords: Vie politique – Oman – 1970-2020

Le M'Zab: Etat des lieux en 1996 - Benyoucef, Brahim (Les Cahiers de l'Epau, 1996)
Keywords: Urbanisme – Mzab

A 'Catalogue of Hebrew Printers' - Hill, Brad Sabin (The British Library Journal, 1995)
Keywords: Judaïsme – Djerba

Sijilmassa: The Rise and Fall of a Walled Oasis in Medieval Morocco - Lightfoot, Dale R.; Miller, James Andrew (Annals of the Association of American Geographers, 1996)
Keywords: Histoire – Sidjilmassa

Grave types and "triliths" in Dhofar - Shahrî, Ali Ahmad Ali Mahāsh al- (Arabian Archaeology and Epigraphy, 1991)
Keywords: Archéologie – Oman

Afrique (L'année épigraphique, 1990)
Notice 1032 : Houmt Souk, dans l'ile de Jerba. Plaque de marbre blanc, tres fragmentaire : 16 à 18x29x3 cm. Lettres de 4,5 a 4 cm. A. Beschaouch, C.R.A.I., 1986, p. 541-543 ; photo, fig. 4. [? ?|] it trium\[f]atori semper Augfusto) \d euota respublica \Girbitana nfumini) [mfaiestati)qfue) eius]. Dedicace a un empereur de l'epoque postconstantinienne, peut etre Valentinien, faite par la respublica de Girba (cite distincte de Meninx) qui a du connaitre un essor au ive s. et donner son nom a l'ile elle-meme.
Keywords: Archéologie – Djerba

Der koranische Kommentar des Ibaditen Hud b. Muhkim/Muhakkam - Gilliot, Claude (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1995)
Keywords: Coran – Commentaires – 9e siècle

Paul-Marie Duval (1912-1997) - Goudineau, Christian (Annuaire du Collège de France, 1996)
Keywords: Archéologie – Djerba

Oman: le Sultanat sentinelle - Kutschera, Chris (Thalassa, 1990)

Nouvelle interprétation du processus de peuplement dans le massif du Hoggar à partir des géographes arabes - Belhachemi, Faouzia (Revue de Géographie Alpine, 1991)
Keywords: Peuplement – Hoggar

L’itinéraire d’une lignée issue de Sidi Muhammad al Kunti As-Saghir (XV°-XVI° siècles) depuis le Sahara occidental jusqu’au Damagaram - Belhachemi, Faouzia (Revue de Géographie Alpine, 1994)
Keywords: Commerce transsaharien

الدور البريطاني في عقد اتفاقية السيب عام 1920 بين سلطان مسقط والامام غي داخلية عمان - فاضل محمد الحسيني (حولية كلية الإنسانيات والعلوم الإجتماعية, 1996)
Keywords: Traité de Sib

التنافس السعودي البوسعيدي - الجهني, عويضه بن متيريك (الدارة, 1997)
تناول البحث قوتين سياسيتين رئيستين برزتا على طول الساحل الشرقي لشبه الجزيرة العربية في بداية القرن الثالث عشر الهجري/ أواخر القرن الثامن عشر الميلادي هما: الدولة السعودية وحكومة مسقط البوسعيدية، وكان إلى جانبهما قوتان أخريان هما: الاتحاد القاسمي، ومشيخات العتوب؛ وقد تنافست القوتان الأوليان في التوسع على حساب نفوذ القوتين الأخريين وغيرهما من قبائل جنوب غرب الخليج العربي. ورمى البحث إلى الإسهام في معرفة الظروف التي دفعت كلا من الدولة السعودية وحكومة مسقط إلى التنافس على كسب ولاء قبائل جنوب غرب الخليج العربي، والدوافع التي وجهت مواقف تلك القبائل من كلا الدولتين، وتحليل أثر مقتل السيد سلطان بن أحمد حاكم مسقط على مسار التنافس وعلى مواقف القواسم والعتوب وأهل الظاهرة منه؛ وحددت الفترة الزمنية للبحث لأنها شهدت بداية التنافس والاحتكاك بين الدولة السعودية وحكومة مسقط، وتمثل نهايتها مقتل السيد سلطان بن أحمد ونتائجه وقد استهل بتناول ظهور البوسعيديين وحكومة مسقط، متطرقا إلي ضعف نفوذ اليعاربه حكام عمان، وتنازعهم على الإمامة، فانقسام القبائل العمانية في أواخر النصف الأول من القرن الثاني عشر الهجري، وبروز أحمد بن سعيد البوسعيدي حاكم صحار، واختيار العمانيين له إماما عام 1162هـ، وكان ذلك بداية تأسيس أسرة حاكمة جديدة في عمان هي أسرة البوسعيديين، وقد غدت مسقط في عهده مركزا تجاريا مهمًا، وخلف سعيد أباه ولم يكن يدرك التحول الذي تمر به عمان، وظل في عاصمته الرستاق في الداخل، فبادر ابنه أحمد بالقبض على زمام الأمور في مسقط وأغلب الأقاليم العمانية والساحلية وزنجبار، وهكذا اقتسمت البلاد العمانية حكومتان حكومة الإمام في الرستاق والداخل، وحكومة مسقط التي عنيت بتطوير أسطولها وتجارتها البحرية؛ وانقسمت البلاد بعد وفاة السيد أحمد عام 1206هـ، فاستقل قيس بصحار، ومحمد بالسويق، وسلطان بمسقط وبركة والمصنعة والساحل، والإمام سعيد بالرستاق. وقد اهتم سلطان بن أحمد بتطوير قوته البحرية وأسطوله التجاري وبتوسيع نفوذه السياسي والتجاري، وأصبحت مسقط العاصمة السياسية لعمان والمركز الرئيسي لتبادل التجارة بين حوض الخليج العربي، والهند والبحر الأحمر وشرق أفريقيا، وتمخض عن توجهات سلطان بن أحمد إلى إهمال أمور الإمامة والقبائل والأقاليم الداخلية، وأخذت عمان تتعرض لضغوط سياسية وعسكرية من داخل الجزيرة العربية مارستها الدولة السعودية. وتناول الباحث ظهور الاتحاد القاسمي ونشاط شيوخ القاسم الذين تنبهوا إلى أهمية السيطرة على مدخل الخليج العربي وجزره. كما تناول ظهور مشيخات العتوب وأبرزها آل صباح وآل خليفة وآل جلاهمة؛ وقد أقام العتوب قوة تجارية وسياسية على الساحل الغربي للخليج العربي خلال النصف الثاني من القرن الثامن عشر الميلادي، وتناول ظهور الدولة السعودية في نجد وامتداد نفوذها إلى شرق جزيرة العرب، متطرقا لبروز دعوة الشيخ محمد بن عبدالوهاب السلفية ومؤازرة الأمير محمد بن سعود حاكم الدرعية للدعوة، وتوجه مجهودات الشيخ محمد بن عبدالوهاب والأمير محمد بن سعود وابنه الإمام عبدالعزيز بن محمد بن سعود لنشر الدعوة وتطبيق مبادئها بتوحيد الأقاليم النجدية تحت مظلة حكومة مركزية في أواخر القرن الثاني عشر للهجرة هي الدولة السعودية، التي برزت خلال العقد الثاني من القرن الثالث عشر للهجرة بصفتها قوة سياسية وعسكرية عظيمة، امتد نفوذها إلى أغلب أقاليم شبه الجزيرة العربية. وقد تزامن بروز وتوسع الدولة السعودية مع ظهور وازدهار دولة البوسعيديين في عمان ومسقط والاتحاد القاسمي في شمال عمان ومشيخات العتوب التجارية في الكويت وقطر والبحرين؛ وبما أن الدولة السعودية وحكومة مسقط كانتا أقوى كيانين سياسيين فإنهما قد دخلا طرفين في تنافس، وسباق للسيطرة على الأقاليم والقبائل والكيانات السياسية الأخرى على الساحل الغربي للخليج العربي. وتناول امتداد النفوذ السعودي إلى مستوطنات العتوب، وإلى عمان الصير، وقد تحالف القواسم مع الدولة السعودية وجعلوا ولاءهم لها، وهاجموا معها حكومة مسقط، وكان أهل الظاهرة وزعيمهم من أبرز حلفاء الدولة السعودية، وقد أسهموا في دعم الحامية السعودية في البريمي، وامتداد النفوذ السعودي إلى عمان، وقد انتهى البحث بخاتمة أبرزت حرص قادة الدولة السعودية على نشر الدعوة السلفية، ومد نفوذهم السياسي على قبائل وموانئ جنوب غرب الخليج وعمان، ورجحان كفة السعوديين في منافستهم للبوسعيديين على كسب ولاء قبائل جنوب غرب الخليج ومد نفوذهم إلى مسقط، بفضل تفوق قواتهم البرية، وانتشار الدعوة السلفية بين قبائل شمال عمان والظاهرة، ومساندة العتوب والقواسم الذين رأوا في قوة الدولة السعودية دعما قويا يساعدهم على التخلص من سيطرة حكومة مسقط.
Keywords: Relations – Oman – Arabie Saoudite

Cheikh Abou Al-'abbas Ahmed (al-Chaykh Abû al-'Abbâs Ahmad, Muhammad b. Bakr al-Forsta'î al-Nufûsî), al Qisma wa 'usûl al 'aradayn kitâb fi fiqh al-'amâra al-islâmiyya: «La division et les fondements des sols", édition al-Turâth al-Qarâra, 1997, 635 p., (ouvrage en langue arabe). - Benyoucef, Brahim (Annuaire de l'Afrique du Nord, 1997)
Keywords: Fiqh – Urbanisme; Furṣuṭāʾī; Aḥmad b. Muḥammad; Recension

Les entrepreneurs migrants d'Europe : dispositifs communautaires et économie ethnique. Le cas des entrepreneurs tunisiens en France - Boubakri, Hassan (Cultures & conflits, 1999)
Keywords: Emigration – Djerba – France

Pierre Cadenat (1902-1998) - Souville, Georges (Antiquités africaines, 1999)
Keywords: Archéologie – Tahert

Sticks and stones: colonialism and Zanzibari housing - Myers, Garth Andrew (Africa, 1997)
Abstract It has become commonplace for scholars to speak of cities, especially colonial cities, as texts in which power relations are embedded. This article presents the findings of six years' research, including archival research, interviewing and fieldwork on the planning and development of Zanzibar. I concentrate on house-building and domestic environments in the city's historic African neighbourhoods, known as Ngʼambo, or the ‘Other Side’. Struggles for cultural hegemony are evident in struggles over Zanzibar's built environment during the twentieth century. The focus is on how the legal language defining house types and establishing building codes, developed under colonialism, became a tactical instrument of the powerful in asserting spatial dominance. Yet the enforcement of the building code often showed the limits of colonial and local elite attempts at hegemony, especially at the end of the colonial era. Throughout the century, the words for African traditional housing and neighbourhood types in Zanzibar have betrayed the disdain with which the powerful have viewed them. There is, however, an order and plan to the ‘unplanned building’ which still dominates the city. , Résumé Il est devenu banal pour les érudits de parler des villes, particulièrement des villes coloniales, en tant que textes dans lesquels les rapports de pouvoir sont incrusté. Cet article présente les données de six années de recherches, y compris des recherches d'archive, des entrevues, et des enquêues de terrain sur la planification et le developpement à Zanzibar. Je me concentre sur le bâtiment des maisons et les environnements domestiques dans les quartiers africains historiques de la ville, connus comme Ngʼambo ou ‘l'autre côté’. La lutte pour l'hégémonie culturelle est évidente dans les conflits concernant le milieu bâti à Zanzibar pendant le vingtième siècle. Le centre d'interêt est sur la façon dont le langage officiel qui définit les types de maison et établit les codes de construction, qui avaient été développés sous le colonialisme, étaient devenu un instrument tactique de la part de ceux qui sont puissant pour imposer la domination de l'espace. Cependant, la mise en vigueur des codes de construction a souvent démontré la limitation des efforts de l'élite coloniale et locale quant à avoir l'hégémonie, surtout à la fin de la période coloniale. A travers le siècle, les mots pour l'habitat traditionnel africain et les types d'habitats dans les quartiers de Zanzibar ont laissé voir le dédain avec lequel ceux qui sont puissant les avaient traité. Il y a cependant un ordre et un plan de la ‘ville non-planifiée’ qui domine toujours la ville.
Keywords: Zanzibar

وجهة نظر أباضیة فی الفرق الإسلامیة - الحديثي, نزار عبد اللطيف (المجمع العلمی العراقی, 1998)

Some Observations on the First Amazigh World Congress (August 27-30, 1997, Tafira, Canary Islands) - Kratochwil, Gabi (Die Welt des Islams, 1999)
Keywords: Berbérisme – Afrique du Nord

Robin Leonard Bidwell 1929-94 - Smith, G. Rex (British Journal of Middle Eastern Studies, 1994)
Keywords: Biographies – Royaume-Uni

Commentaire à la note de Nadjib Ferhat, Karl Heintz Striedter et Michel Tauveron. Une limite ante quem pour l'art bubalin du Sahara central C.R. Acad. Sci. Paris, Tome 324, série Ila, 1997, pp. 75-77 - Quellec, Jean-Loïc Le (Comptes Rendus de l'Académie des Sciences - Series IIA - Earth and Planetary Science, 1997)
Keywords: Art rupestre – Mzab

Les Zanzibarites et le Burundi XIXe-XXe siècle - Gahama, Joseph (Omaly Sy Anio, 1994)
Keywords: Zanzibar

Les Juifs du Maghreb au XIXe siècle. Aperçus de démographie historique et répartition géographique - Taïeb, Jacques (Population, 1992)
Keywords: Judaïsme – Djerba

Prehistoric Tower Tombs at Shir/Jaylah, Sultanate of Oman - Yule, Paul A.; Weisgerber, Gerd (Beiträge zur allgemeinen und vergleichenden Archäologie, 1998)
In 1995 survey was undertaken in the Sultanate of Oman in order to monitor the preservation to archaeological monuments. The work centred on over 58 tombs at Shir (Wilīyat Ṣūr). Five types of tombs were discerned. In their form and manner of building the towers the so-called beehive tombs of the Hafit Period, but also share certain resemblances with collective Umm an-Nar period tombs.
Keywords: Archéologie – Oman

Tippo Tip à Mulongo. Nouvelles données sur le début de la pénétration arabo-swahili au Sahara - Maret, Pierre de; Legros, Hugues (Civilisations. Revue internationale d’anthropologie et de sciences humaines, 1993)
The tribal lands of the Luba of Mulongo, situated at the extreme north of the Upemba depression are not only an almost obligatory point of passage for those coming from the east en route to the heart of the Luba but are also an important market. It is therefore a very useful place to study the Arab-Swahili penetration in the kingdom of Luba in the nineteenth century, especially as one of the first merchants to reach this chefferie was none other than Tippo Tip. In his autobiography, he briefly speaks of his incursions in Luba but up to now, no other source has permitted the verification or the completion of the information provided by Tippo Tip.An unpublished administrative report dating from 1909, written up from the oral tradition of the precedent century, tells of power struggles between two rival lineages of the Mulongo royalty. The report not only provides a complete ancestry of the chiefs but also allows the accurate dating of the stages of Arab-Swahili penetration in the kingdom of Luba. Furthermore, this document refers to the passage of Tippo Tip in the region and gives us much information regarding the events that took place during his stay. The congruence of the sources enables a relatively detailed chronology of the passage of Tippo Tip to be established and a better definition of the forms of the penetration and the political domination of Arab-Swahili at the heart of the Luba empire.
Keywords: Tippo Tip (1837-1905); Zanzibar

Desert Cities: Ghardaia, a city of stone and Shibam, a city of clay - Laureano, Pietro (World Heritage Review, 1998)

The Samad Period in the Sultanate of Oman - Yule, Paul A. (Iraq, 1999)
Keywords: Archéologie – Oman

More than Samad in Oman: Iron Age pottery from Suhar and Khor Rori - Yule, Paul A.; Kervran, Monique (Arabian Archaeology and Epigraphy, 1993)
Keywords: Archéologie – Oman

Contribution au débat sur le peuplement du Hoggar - Rey, Pierre-Philippe (Revue de Géographie Alpine, 1992)

Le polymorphisme de l’ADN mitochondrial révèle une différenciation génétique entre certains groupes ethniques de la population de Jerba - Yacoubi Loueslati, Besma; Ennafaa, Hajer; Ben Amor, Mohamed; Heyer, Evelyne; Langaney, André; Ben Ayed, Farhat (Archives de l'Institut Pasteur de Tunis, 1998)
Jerba is an island situated in the South - East of Tunisia were some ethnic groups (Arabs, Berbers, Blacks, Jewishs and others) cohabit for centuries. The religion and cultural differences have represented an obstacle to a mixture between these groups.
Keywords: Génétique – Djerba

An Arabic Deed of Sale from Swahili Mombasa Dated 1292/1875 - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 1993)
Keywords: Zanzibar

Mombasa under the BuSa'idi : A Leaf from the Taylor Papers (SOAS MS 47757, folio 50) - Frankl, P.J.L. (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1991)
Keywords: Zanzibar

Shu'ba b. al-Ḥajjāj (d. 160/776) and his Position Among the Traditionists of Baṣra - Juynboll, Gautier H. A. (Le Muséon, 1998)
The man who is the subject of this paper occupies a foremost position among the most famous Ìadith collectors of Baṣra, and it is with his
Keywords: Hadith – Exégèse – Irak

'Even an Ethiopian Slave': The Transformation of a Sunnī Tradition - Crone, Patricia (Bulletin of the School of Oriental and African Studies, 1994)
Keywords: Gouvernance – Kharijisme

Review: Oman: Politics and Development, by Ian Skeet. New York: St. Martin's Press, 1992. xvii + 163 pages. Append. to p. 164. Notes to p. 183. Bibl. to p. 186. Index to p. 195. $49.95. - Landen, Robert Geran (Middle East Journal, 1993)
Keywords: Recension

Symposium: Contemporary Oman And U.S.-Oman Relations - Pelletreau, Robert H.; Page, John; Kechichian, Joseph Albert; Geyer, Georgie Anne; Eickelman, Christine; Dunn, Michael Collins (Middle East Policy, 1996)
Keywords: Relations – Oman – Etats-Unis

Local Economy and Long Distance Trade in Medieval Sijilmasa - Messier, Ronald A (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 1993)
Keywords: Commerce transsaharien

Das Tal des Oued M'zab (Algerien). Zur Entstehung eines Balungsraumes in der Wüste - Baouni, Tahar (Mitteilungen der Geographischen Gesellschaft in München, 1998)
Keywords: Géographie – Mzab

Aden-Mascate-Zanzibar D'après la correspondance inédite d' Emile Kuhlmann, drogman-chancelier au consulat de France à Zanzibar (1849-1856) - Hueber, Régis (Chroniques Yéménites, 1995)
Keywords: Relations – Zanzibar – France

Le Iscrizioni Nelle Moschee Di Manaḥ (sultanato Di Omàn) - Baldissera, Eros (Quaderni di Studi Arabi, 1990)
Keywords: Architecture – Oman

The Sultan of The Arab State of Zanzibar and The Regent 1902-1905 - Saud, Turki Benyan (Journal of the Documentation and Humanities Research Center, 1997)
Keywords: Zanzibar

Review : Joseph A . Kechichian, Oman and the World, the Emergence of an Independent Foreign Policy, RAND, 1700 Main Street, Santa Monica, California, 12/1995, 400 pp. - Sanguineti, Vittorio (East and West, 1996)
Keywords: Recension

Il Sultanato di Oman ed il mondo (1970-1995) in un'analisi di Joseph A. Kechichian - Sanguineti, Vittorio (Rivista di Studi Politici Internazionali, 1996)
Keywords: Politique étrangère – Oman – 1970-2020

Zu den Ḫuṭab des Abū Ḥamza Aš-Šārī in der Klassischen Arabischen Literatur - Dähne, Stephan (Hallesche Beiträge zur Orientwissenschaft, 1998)
Keywords: Sermons – Ibadisme

Review: Plants of Dhofar: The Southern Region of Oman. Traditional, Economic and Medicinal Uses - Cope, T. A. (The Geographical Journal, 1990)
Keywords: Dhofar; Recension

Les Mozabites face à la crise algérienne - Boudi, Salah (Hérodote, 1994)

Omani maritime trade and the Indian residents of Muscat in the 18th and beginning of the 19th centuries - Fukuda, Sadashi (Orient, 1992)

Iron Age Gao: An Archaeological Contribution - Insoll, Timothy (The Journal of African History, 1997)
Keywords: Archéologie – Mali

Gao and Igbo-Ukwu: Beads, Interregional Trade, and Beyond - Insoll, Timothy; Shaw, Thurstan (The African Archaeological Review, 1997)
Keywords: Archéologie – Mali

En hommage à Jean Lethielleux 1900-1998 - Breteau, Claude H.; Roth, Arlette (Littérature orale arabo-berbère, 1999)
Keywords: Biographies – France

Batinah Coast of Oman - Melamid, Alexander (Geographical Review, 1990)
Keywords: Géographie – Oman

Mihrabs omanais du 16e siècle: un curieux exemple de conservatisme de l'art du stuc iranien des époques seldjouqide et mongole - Kervran, Monique; Bernard, Vincent (Archéologie Islamique, 1996)
Keywords: Archéologie – Oman

Deux siècles de relations franco-omanaises (1735-1920) Aperçu historique - Oddos, Robert (Revue Historique, 1996)
Keywords: Relations – Oman – France

Jebel Akhdar and Dhofar: footnote to empire - Newsinger, John (Race & Class, 1998)
Keywords: Dhofar

Communal Organization of the Jews of Tripolitania during the Late Ottoman Period - Goldberg, Harvey E. (Jewish Political Studies Review, 1993)
Keywords: Judaïsme – Djebel Nefousa

Security in the Gulf. The view from Oman - Bahgat, Gawdat (Security Dialogue, 1999)
Keywords: Politique étrangère – Oman – 1970-2020

early Islamic family from Oman: al-'Awtabi's account of the Muhallabids. By Martin Hinds (Journal of Semitic Studies Monograph No. 17.) pp. vii, 97. Manchester, Journal of Semitic Studies, University of Manchester, 1991 - Hawting, Gerald R. (Journal of the Royal Asiatic Society, 1993)
Keywords: Recension

Mass Higher Education and the Religious Imagination in Contemporary Arab Societies - Eickelman, Dale F. (American Ethnologist, 1992)

Fertility and Social Change in Oman: Women's Perspectives - Eickelman, Christine (Middle East Journal, 1993)

Libraries and library education in Oman - Mufaraji, Moosa N. al- (Journal of Information Science, 1992)
This article surveys the current status of librarianship in the Sultanate of Oman Similar to any other developing country, Oman faces problems in librarianship, such as shortage of professional librarians, lack of well-equipped libraries, and the absence of a professional library organisation. The article deals with the various types of existing libraries in the Sultanate, with emphasis on the Sultan Qaboos University Libraries, the largest in the country It also reviews the foundation of the Librarianship and Documentation Department at Sultan Qaboos University and discusses other informal training programmes for librarians.
Keywords: Bibliothèques – Oman

Review: Oman: Politics and Development, by Ian Skeet. 195 pages, tables, photos, glossary, notes, bibliography, index. New York: St. Martin's Press, 1992. $49.95 (Cloth) isbn 0-312-06886-7 - Anthony, John Duke (Middle East Studies Association Bulletin, 1993)
Keywords: Recension

La communauté juive de Djerba ; secrets d’une pérennité - Qabla, Gabriel (Confluences Méditerranée, 1994)
Keywords: Judaïsme – Djerba

Hebrew Elements in the Spoken Arabic of Djerba - Henshke, Yehudit (Massorot: Studies in Language Traditions and Jewish Languages, 1991)
Keywords: Judaïsme – Djerba

Combien de Juifs en Tunisie et en Libye (1850-1970) ? - Taïeb, Jacques (Revue des études juives, 1999)
Keywords: Judaïsme – Djebel Nefousa

Islam in Italy and in Its Libyan Colony (720-1992) - Kopanski, Ataullah Bogdan (Islamic Studies, 1993)

Review : DAWN CHATTY, Mobile Pastoralists: Development Planning and Social Change in Oman (New York: Columbia University Press, 1996). Pp.230. - Jennings, Anne M. (International Journal of Middle East Studies, 1997)
Keywords: Recension

رسالة في بيان كل فرقة لأبي عمرو عثمان بن خليفة السوفي المارغني الإباضي - عامر, ونيس الطاهر (مجلة جامعة الزيتونة, 1994)
Keywords: Hérésiographie – Ibadisme

Chasseurs et pasteurs du Messak Settafet (Fezzan - Libye) - Van Albada, Axel; Van Albada, Anne-Michelle (Préhistoire Anthropologie Méditerranéennes, 1992)
Keywords: Archéologie – Djebel Nefousa

Settlement space and architecture in South-Arabian oases: preliminary remarks on the use and division of space in Omani oasis settlements - Mershen, Birgit (Proceedings of the Seminar for Arabian Studies, 1999)
Keywords: Architecture – Oman

Review: Merchants & Faith: Muslim Commerce and Culture in the Indian Ocean, by Patricia Risso. (New Perspectives on Asian History) 152 pages, maps, notes bibliography, index. Boulder, CO: Westview Press, 1995. $15.95 (Paper) isbn 0-8133-8911-9 - Nicolini, Beatrice (Middle East Studies Association Bulletin, 1996)
Keywords: Recension

[Francesco Gabrieli (1904-1996)] - Jacono, Claudio Lo (Oriente Moderno, 1997)
Keywords: Orientalisme – Italie

al-Jumhūriyya al-Ṭarāblusiyya - Rayyān, Muḥammad Rajā’ī (Revue d'Histoire Maghrébine, 1993)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

Dawr al-Imām Bayyūḍ fī ‘l-Nahḍa al-Waṭaniyya al-Jazā’iriyya wa-Muqārana bi’l-ʿAllāma bin Bādīs - Qarqab, ʿĪsà (Revue d'Histoire Maghrébine, 1997)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Recent Ibāḍī writings - Vikør, Knut S. (Saharan Studies Association Newsletter, 1993)
Keywords: Recension

Khalīfa b. ʿAskar al-Nālūtī (1878-1922) - Lissir, Fethi (Revue d'Histoire Maghrébine, 1995)
Keywords: Biographies – Djebel Nefousa – 20e siècle

Les Kānoūn des Beni-Mzab - Masqueray, Emile (Études et Documents Berbères, 1995)
Keywords: Droit coutumier – Mzab

عمان الداخل من 1507 -1624م التركيبة القبلية والسياسية - النابودة, حسن محمد عبدالله (الوثيقة, 1992)
Keywords: Vie politique – Oman – 15e siècle

The commercial activity of Bahrain and Oman in the early Middle Ages - Nābūda, Ḥasan Muḥammad al- (Proceedings of the Seminar for Arabian Studies, 1992)
Keywords: Relations – Oman – Bahrein

Die Masā’il Nāfiʿ b. al-Azraq - Element des “Portrait mythique d’Ibn ʿAbbās” oder ein Stück realer Literatur? Rückschlüsse aus einer bisher unbeachteten Handschrift - Neuwirth, Angelika (Zeitschrift Für Arabische Linguistik, 1993)
Keywords: Azraqisme

A 12th/18th century Swahili letter from Kilwa Kisiwani (being a study of one folio from the Goa Archives) - Omar, Yahya Ali; Frankl, P.J.L. (Afrika und Übersee, 1994)
Written in 1711, about a decade after the Omanis occupied the island, by Faṭima binti Muḥammad, addressed to Mwinyi Jumaa, probably from Mombasa.
Keywords: Zanzibar

Anglo-American rivalry in the Middle East: the struggle for the Buraimi oasis, 1952-1957. - Petersen, Tore Tingvold (The International History Review, 1992)
On British-American controversy over the Saudi claim to the Buraimi oasis

Percorsi commerciali nell’Oceano Indiano occidentale: Zanzibar nel 1800 - Nicolini, Beatrice (Quaderni Asiatici, 1999)
Keywords: Zanzibar

Little known aspects of the history of Muscat and Zanzibar during the first half of the nineteenth century - Nicolini, Beatrice (Proceedings of the Seminar for Arabian Studies, 1997)
Keywords: Zanzibar

The source of spice: Oman, Zanzibar and Europe during the nineteenth century - Nicolini, Beatrice (ARAM Periodical, 1996)
Keywords: Zanzibar

al-Shaykh ʿAbdallāh al-Bārūnī. Dirāsa fī Akhbārihi wa-Āthārihi - Jibrān, Muḥammad Masʿūd (Revue d'Histoire Maghrébine, 1993)
Keywords: Biographies – Djebel Nefousa – 20e siècle

Kitābāt Sulaymān al-Bārūnī al-Tārīkhiyya - Jibrān, Muḥammad Masʿūd (Revue d'Histoire Maghrébine, 1992)
A discussion and analysis of Sulaymān’s annotations to his fatḥer’s Sullam al-ʿĀmma wa’l-Mubtadi’īn, Sulaymān’s al-Azhār al-Riyāḍiyya, his Mukhtaṣar Tārīkh al-ʿĀ’ila al-Bārūniyya, and his uncompleted project of writing a history of the Tripolitanian war.
Keywords: Bārūnī; Sulaymān al- (1870-1940)

man huwa Abū Muḥammad al-ʿUmānī - Banʿalī, Banʿalī Muḥammad Būzayyān (نزوى: مجلة فصلية ثقافية, 1999)
Keywords: Biographies – Oman

Ḥamlat al-Imām al-Ṣalt b. Mālik ʿalà Jazīrat Sūquṭrà wa’l-ʿAlāqāt al-ʿUmāniyya al-Mahriyya - Ubaydli, Ahmad (نزوى: مجلة فصلية ثقافية, 1998)

al-Siyar al-ʿUmāniyya ka-Maṣdar li-Tārīkh ʿUmān. Sīrat Muḥ. b. Maḥbūb - Ubaydli, Ahmad (نزوى: مجلة فصلية ثقافية, 1995)

al-Ḥayāt al-Adabiyya fī ʿUmān ḥattà ʿĀmm 134 H. - Sāmarrā’ī, Muḥammad Rajab al- (نزوى: مجلة فصلية ثقافية, 1998)
Keywords: Vie culturelle – Oman

Samā’il, Ḥāḍirat al-ʿIlm wa’l-Adab - Maʿmarī, Ṭālib al- (نزوى: مجلة فصلية ثقافية, 1998)
Keywords: Vie intellectuelle – Oman

Abzūn, al-Fārisī alladhī taʿammana: al-Huwiyya wa’l-Ahammiyya - Maḥrūqī, Muḥammad al- (نزوى: مجلة فصلية ثقافية, 1997)

Abū Muslim al-Bahlānī, Rā’id al-Shiʿr al-ʿUmānī al-Ḥadīth - Maḥrūqī, Muḥammad al- (نزوى: مجلة فصلية ثقافية, 1996)
Keywords: Poésie – Oman

‏قراءة في أسباب انتصار العمانيين في معركة سلوت - بوتشيش, إبراهيم القادري (نزوى: مجلة فصلية ثقافية, 1998)
Keywords: Conflits – Oman

Sayyid Khālid b. Barghash: drei Tage Sultan - dreissig Jahre im Exil - Schneppen, Heinz (Der Islam, 1999)
Keywords: Zanzibar

Ibāḍī-Jewish parallels in early medieval North Africa - Savage, Elizabeth (Al-Masāq, 1992)

Iraqi Christian links with an early Islamic sect - Savage, Elizabeth (ARAM Periodical, 1994)

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Zaman, Muhammad Qasim (Journal of the Royal Asiatic Society, 1999)
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Rebstock, Ulrich (Bibliotheca Orientalis, 1999)
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Bennison, Amira K. (The Maghreb Review, 1999)
Keywords: Recension

ʿUmān and East Africa: the historical significance of an Arabic manuscript by Shaykh al-Amīn b. ʿAlī al-Mazrūʿī - Soghayroun, Ibrahim (Proceedings of the Seminar for Arabian Studies, 1999)

The agrarian economy of Oman (132-280/749-893) in Arabic sources - Ubaydli, Ahmad (Journal of Islamic Studies, 1993)
Conclusion (p. 48): the agrarian system which existed in Oman in the period under consideration (the first Ibāḍī state, 132-280/749-893), together with fishing and pearling and maritime trade, enabled the country to establish a base for economic self-reliance. This was manifested in a tendency to resist central authority. The Aflāj irrigation system in its Omani context made it possible for its users to be more independent and to have more influence over the local authorities. Ibāḍism seems to have reflected these two tendencies well enough for the Omanis to adopt it. Both classical Arabic and Omani sources reflect this situation and, taken together, provide a detailed description which illuminates various aspects of the agrarian economy that existed in Oman during this period.
Keywords: Agriculture – Oman

Iḍā’āt min al-Shiʿr al-ʿUmānī - Hajri, Hilal al- (نزوى: مجلة فصلية ثقافية, 1999)
Poetry of: Muḥ. b. ʿAbdl. al-Maʿwalī; Hilāl b. Saʿīd b. ʿArrāba; ʿAlī b. Thābit al-Sāsānī; Saʿīd b. Muḥ. al-Kharūṣī al-Ghishrī; Abū ‘l-Shayba Nūr al-Dīn ʿAbdl. b. Ḥumayyid al-Sālimī; Aḥm. b. Sul. b. al-Naẓar.
Keywords: Poésie – Oman

al-Khiṭāb al-Thaqāfī al-ʿUmānī fī Sharq Ifrīqiyā. Al-Taḥlīl al-Naqdī li-Ṣidām Khiṭābayni wa-Dalālātihi al-Ijtimāʿiyya - Ḥarrāṣī, ʿAbdallāh al- (نزوى: مجلة فصلية ثقافية, 1999)
A (very) theoretical analysis of Sālimī, Abū Muḥ. ʿAbdl. b. Humayyid: Badhl al-Majhūd fī Mukhālafat al-Naṣārà wa’l-Yahūd (see Mashriq). As the author puts it, he tried to show the interaction between language and the social context within which language is used, or, in other words, to show the link of language and rhetorics with the social structure of Omani society at the time al-Sālimī wrote this work.

al-Dawla al-Yaʿrubiyya (1624-1744). Manẓūr Khaldūnī - Hinā’ī, ʿAbd al-Malik al-; Ḥarrāṣī, ʿAbdallāh al- (نزوى: مجلة فصلية ثقافية, 1998)
Keywords: Vie politique – Oman – 1624-1742

Le commentaire coranique de Hūd b. Muḥakkam/Muḥkim - Gilliot, Claude (Arabica, 1997)
Pp. 181-182: Hūd’s Tafsīr seems to be a kind of abstract of the Tafsīr of Yaḥyà b. Sallām al-Baṣrī (d. 200/815 in Egypt), who was born in 124/742 in Baṣra and who lived for a period of time in Kairouan. He was accused of being a Murji’ite.
Keywords: Coran – Commentaires – 9e siècle; Hawwārī; Hūd b. Muḥkim al-

Professor Tadeusz Lewicki, January 28, 1906 - November 22, 1992 - Kubiak, Wladyslaw (Rocznik Orientalistyczny, 1997)
Necrology. A list of Lewicki’s works up to 1993 (partly the same as Zajaczkowski, Folia Orientalia, 11, 1969, 7-47) by Wlodzimierz Zajaczkowski and Urszula Lewicka-Rajewska (pp. 11-53). A list of Lewicki’s works prior to 1970 has been published by Zajaczkowski 1969.
Keywords: Lewicki; Tadeusz (1906-1992)

al-Munākh al-ʿIlmī wa’l-Adabī fī Tārīkh Ṣūr - Darwīsh, Aḥmad (نزوى: مجلة فصلية ثقافية, 1996)

al-Shaykh Abū l-Yaqẓān wa-Kitābuhu “Sulaymān al-Bārūnī” - Ḥasanī, Muḥammad al-Hādī al- (Al-Muwāfaqāt, 1996)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Bārūnī; Sulaymān al- (1870-1940)

A Zanzibari waqf of books: the library of the Mundhiri family - O’Fahey, R.S.; Vikør, Knut S. (Sudanic Africa, 1996)
Scattered among the Arabic books and MSS section of the Zanzibar Archives are a number of books written by, or which contain ownership of Waqfiyya notices written by, various members of the Mundhirī family. The Mundhiris were cultivated scholars through at least three generations, who not only collected and endowed MSS, but also wrote them. The family was established in the Malindi quarter of Zanzibar city before Sayyid Saʿīd b. Sulṭān finally settled on the island in 1832. ʿAlī b. Muḥ. al-Mundhirī did most to establish and consolidate the Waqf of books. Although only fragments of his work survive, what we do have gives much information about the intellectual climate in Zanzibar at the end of the 19th century. A list of titles included in the Waqf is included in the article.
Keywords: Zanzibar

Salim b. Zekvan’ın Sîre adlı eserindeki Mürcie ile ilgili kısmın tercümesi - Kutlu, Sönmez (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1994)
[A translation of the part on al-Murji’a in Sālim b. Dhakwān’s work entitled Sīra].

Primitive Islam and architecture in East Africa - Horton, Mark (Muqarna, 1991)
Keywords: Architecture – Zanzibar

Ottoman reaction to the European "scramble for Africa" : the defence of the hinterland of Tripolitania and Cyrenaica - Gall, Michel Le (Asian and African Studies, 1990)
Keywords: Djebel Nefousa – 1551-1911

Le manuscrit no. 277 de l’ancienne collection ibāḍite du feu Zygmunt Smogorzewski de Lwów - Lewicki, Tadeusz (Folia Orientalia, 1990)
Contains K. al-Siyar of Abū ‘l-Rabīʿ Sul. b. ʿAbd al-Salām al-Wisyānī (pp. 1-189), Anonymous: Siyar al-Mashāyikh (pp. 190-344), and no title and no author, but must be a copy of the second part of K. Al-Sīra wa-Akhbār al-A’imma of Abū Zak. Yaḥyà b. Abī Bakr al-Warjlānī (pp. 345-416).
Keywords: Manuscrits – Lviv

Les noms propres berbères employés chez les Nafūsa médiévaux (VIIIe-XVIe siècle). (Observations d’un arabisant). Quatrième partie - Lewicki, Tadeusz (Folia Orientalia, 1990)
Keywords: Linguistique – Djebel Nefousa

Per una storia della stampa in Algeria: da "L’Estafette d’Alger" (1830) ai giornali della Repubblica Algerina Popolare e Democratica (1989) - Manduchi, Patrizia (Oriente Moderno, 1990)
Keywords: Journalisme – Mzab

The Azāriqa in Islamic heresiography - Lewinstein, Keith (Bulletin of the School of Oriental and African Studies, 1991)
Keywords: Azraqisme

Making and unmaking a sect: the heresiographers and the Ṣufriyya - Lewinstein, Keith (Studia Islamica, 1992)
Given the later importance of these Ṣufrite groups as Ibāḍī rivals, the heresiographers had to account for their origins and offer a doctrinal rationale for their existence. It was in this context that Ibn al-Aṣfar and the satellite sects were born (o.c., 96).
Keywords: Hérésiographie – Sufrisme

A tale of three shambas. Shāfiʿī-Ibāḍī legal cooperation in the Zanzibar protectorate. Part I. - Bang, Anne K.; Vikør, Knut S. (Sudanic Africa, 1999)
In this article three cases before the Sultan’s Court for Zanzibar and Pemba are presented over inheritance involving the possession of shambas, farms and farmhouses in the agricultural areas (from the Zanzibar National Archive, files HC8/1-140). For the Ibāḍiyya, the main legal text was K. al-Nīl wa-Shifā’ al-ʿAlīl of ʿAbd al-ʿAzīz b. Ibr. al-Muṣʿabī al-Thamīnī (1130-1223/1718-1808). To this, the most frequently used commentary was Sharḥ al-Nīl by Muḥ. b. Yūsuf Iṭfayyish (1260-1332/1820-1914). Another much used work on Ibāḍī inheritance law was the Mukhtaṣar by the Omani author Abū ‘l-Ḥasan ʿAlī b. Muḥ. al-Bisyawī. Pp. 8-9: information on the Ibāḍī Qāḍī ʿAlī b. Muḥ. al-Mundhirī (1866-1925).
Keywords: Zanzibar

Monumental Evidence of the Ancient Jewish Community at Sohar (Oman) - Costa, Paolo M. (ARAM Periodical, 1999)
Keywords: Judaïsme – Oman

From the individualism to the community’s power: the economic implications of the Wilāya/Barā’a dynamic among the Ibāḍīs - Francesca, Ersilia (Annali dell'Istituto Universitario Orientale di Napoli, 1999)
At the end of the article, p. 75: among the Mozabites, Wilāya and Barā’a represent a religious transformation of tribal politics. The notables’ authority could not exist without a social structure founded in the clan. Each clan designates its representatives in the Jamāʿa and its notables, who direct the group’s business, form a restricted assembly which meets in the presence of one of the members of the Ḥalqa (Bourdieu 1962, 41-42). This connection between religious solidarity and agnatic groups’ power assures that community ties remain very strong even among emigrants. Particularism and individualism are banished and each Ibāḍī has a strong feeling of belonging to “the chosen people”, distinguished by their rigor and intransigence. In terms of organization of entrepreneurial activity, the solidarity existing among the Mozabites is converted into commercial cooperation. The business establishments in the Tell are generally the property of the family group, and in most cases the employees are members of the owner’s family or else come from the same clan or city. This family organization of the business enterprise, thanks to the very limited costs, allows the Mozabites to sell at competitive prices. Moreover, mutual aid is praticed in every possible occasion (Bourdieu 1962, 48; Chabert 1961, 348). In this way, fidelity to the traditional social structure, far from being an obstacle to their competitiveness in the capitalistic system, rather favours it and makes it easier.

Thalāthu Rasā’il Makhṭūṭa ḥawla al-Ibāḍiyya al-Mīzābiyyīn bi’l-Jazā’ir fī ‘l-ʿAhd al-ʿUthmānī - Baḥḥāz, Ibrāhīm (Revue d'Histoire Maghrébine, 1998)
The Ottoman period in Algeria was from 1515-1830. These three letters are from the private library of Muḥ. al-Ḥājj Saʿīd b. Ayyūb in Ghardaïa, Mīzāb. The first letter (Dhū ‘l-Qaʿda 1206/1792) contains a complaint from the Mīzābīs to the Dāy Bābā Ḥasan (1791-1798) about the intention of Ṣāliḥ Bāy, Bāy of Constantine (1771-1792), to subdue the Mīzābīs and their families, to lead their women and children into captivity, and subsequently to exterminate them, probably for no other reason then their belonging to the Ibāḍī Madhhab. The second letter (Muḥarram 1207/Aug. 1792) is a letter of thanks for the Dāy’s help. The third one (end of Ṣafar 1207/1792), to al-Ḥājj ʿAlī b. ʿAbd al-Laṭīf, Siḥr of the Dāy and their mediator with the Dāy, “expresses the acknowledgment of what is beautiful by its writers”; it contains the aforementioned complaint and the Mīzābīs’ gratitude.
Keywords: Emigration – Mzab – Algérie

The dead ostrich. Life and trade in Ghadāmes (Libya) in the nineteenth century - Haarmann, Ulrich (Die Welt des Islams, 1998)
Keywords: Commerce – Ghadames; Droit coutumier – Ghadames

Review : Cilardo, Agostino: (1996) Diritto ereditario islamico delle scuole giuridiche sunnite (Ḥanafita, Malikita, Shāfiʿita e Ḥanbalita) e delle scuole giuridiche Zaydita, Ẓāhirita e Ibāḍita: casistica. Rome/Naples: Istituto per l’Oriente “C.A. Nallino”/Istituto Universitario Orientale, Dpt. di Studi e Ricerche su Africa e Paesi Arabi, 1996, (701 pp., 24x17 cm.). - Rebstock, Ulrich (Die Welt des Islams, 1997)
Keywords: Recension

Les Pays Bas et la guerre de Libye (1911-1912) - Bono, Salvatore (Revue d'Histoire Maghrébine, 1995)
On international diplomatic efforts to put an end to the Italian-Turkish conflict. The Dutch initiative took place mid-December 1911.
Keywords: Invasion italienne – Libye

Les communautés noires du Mzab - Daddi Addoun, Yacine (Saharan Studies Association Newsletter, 1995)
Thesis in progress at the Institut National des Langues et Civilisations Orientales (INALCO), Paris. For reference to the Ibāḍī point of view on slavery, Muḥ. b. Yūsuf Iṭfayyish’ work Sharḥ al-Nīl wa-Shifā’ al-ʿAlīl is used.

Arabizing the Omani intelligence services: Clash of cultures? - Eickelman, Dale F.; Dennison, M. G. (International Journal of Intelligence and CounterIntelligence, 1994)
Keywords: Vie politique – Oman – 1970-2020

Review: Schwartz, Werner: (1986) Kitāb Ibn Sallām. Eine ibāḍitisch-maghribinische Geschichte des Islams aus dem 3./9. Jahrhundert. Hrsg. von Werner Schwartz und Shaikh Sālim ibn Yaʿqūb. Wiesbaden: Franz Steiner Verlag (in Kommission von: Orient Institut der Deutschen Morgenländischen Gesellschaft, Beirut), 1986, (168 pp., 24,5x17,5 cm.). ISBN 3-515-04497-3. - Adīb, D. (Mideo, 1993)
Keywords: Recension

Mosques, merchants and landowners in Zanzibar stone town - Sheriff, Abdul Mohamed Hussein (Azania: Archaeological Research in Africa, 1992)
In the old “stone town” of Zanzibar west of the former creek there are about fifty mosques, mostly built during the 19th century. By studying these mosques, this paper reconstructs the growth and economic and social history of the town. It demonstrates that merchants as well as landowners supported the construction of mosques and that the construction of mosques was an important aspect of urban development. An examiniation of the growth of Zanzibar town shows that, from the latter part of the 18th century, Zanzibar began to develop as the centre of a commercial empire based on the twin foundations of transit trade and plantation agriculture. The history of the mosques can be divided into several phases, of course with some overlap. First the Sunnī mercantile tradition and the mosques built during this phase are described. By the 1840s, a new phase is discernible in mosque construction, a phase dominated by the Ibāḍī tradition with its unique architectural features reflecting Ibāḍī dogmas and practices. Finally, attention is paid to Ibāḍī-Sunnī interaction (Catalogue African Studies Centre, Leiden). At Zanzibar, the Ibāḍīs were a minority sect that tended to be gradually absorbed by the Shāfiʿī denomination. Generally the two denominations lived together in perfect harmony. Only under Sultan Barghash b. Saʿīd (Sultan 1870-1888), who was under the influence of the Ibāḍī Imamate movement in Oman, an Ibāḍī Nahḍa occurred which lead to some tension between Ibāḍīs and Sunnīs (pp. 17-19).
Keywords: Zanzibar

Muslim land and water law - Wilkinson, John Craven (Journal of Islamic Studies, 1990)

La guerra italo-tripolina nelle “Memorie” di Suleiman al-Baruni - Del Boca, Angelo (Studi piacentini, 1992)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

Aḍwā’ ʿalà Maṣādir al-Tārīkh al-ʿUmānī al-Ḥadīth (al-ʿUmāniyyūn fī Muwājahat al-Wujūd al-Burtughālī. Dirāsa fī Maṣādir al-Tārīkh al-ʿUmānī) - ʿArab, Muḥammad Ṣābir (نزوى: مجلة فصلية ثقافية, 1997)

Entering the exciting: the distinctive features of al-Ibāḍīya - Vehkavaara, Mikko (Studia Orientalia, 1997)
Based on research at Jerba and Zanzibar. Deals in part with the issue of whether al-Ibāḍiyya forms part of al-Khārijiyya. Gives considerations about what al-Ibāḍiyya really is. Among the author’s sources are Muʿammar 1988 and Quṭbiyya 1992. P. 140 note 28: while Sachau 1894 could write at the end of the nineteenth century that Zanzibar had eight Ibāḍī and two Shāfiʿī judges, presently there is one judge for each of the ten districts plus a chief Qāḍī and an assistant chief Qāḍī, which makes a total of 12 judges, the majority of whom are Shāfiʿīs. And to make the task of the Zanzibari legal counsellors even more difficult, they not only have to keep up with the latest Ibāḍī scholarship but also be informed in the doctrines of the other Muslim minorities, such as the Shīʿite ones. Stockreiter 2002, 52, writes that after the revolution, which put an end to the reign of the Sultan, Ibāḍī judges and Ibāḍī courts were abolished.

Le rôle des arabes dans les révoltes des berbères khāridjites (IIe siècle Hégire-VIIIe siècle) - Ghali, Abdelkader el- (Cahiers de Tunisie, 1996)
Keywords: Invasion arabe – Afrique du Nord

Review : Biancifiori — Works of Architectural Restoration in Omanby Maria Antonietta Biancifiori - Baldissera, Eros (Quaderni di Studi Arabi, 1996)
Keywords: Architecture – Oman; Recension

Family strife and foreign intervention: causes in the separation of Zanzibar from Oman: a reappraisal - Bhacker, M. Reda (Bulletin of the School of Oriental and African Studies, 1991)
The nineteenth-century rise of Zanzibar under the ruling Albusaidi Dynasty of Oman owed its origins primarily to the solid foundations of commercial activity laid down in Muscat in the preceding century. In the subsequent development of the Omani economy, in Omani territories in both Arabia and Africa where the dictates of the Omani political/tribal system did not allow for any centralization of authority, local communities and tribal groups resisted the domination of the Albusaidi rulers as they strove to bring under their own control the benefits of burgeoning trade. The opposition of the major Omani groups in East Africa, the Mazāri‘a of Mombasa and the Banū Nabhān of Pate, to the Albusaidis and the eventual success of the Omani rulers in dismantling and neutralizing this opposition are fairly well documented. However, the sustained challenge of Hilāl b. Sa‘īd to the reign of his father Sa‘īd b. Sulṭān, the Albusaidi ruler of Oman and Zanzibar and their dependencies from 1806 to 1856, has hitherto been neglected, despite the fact that Hilāl's resistance in East Africa was the greatest internal threat to Sa‘īd after that posed by the Mazāri'a and had dire consequences for the subsequent course of Oman's history. The conflict between father and son set in train a course of events that led inexorably to the 1861 British-sponsored dismemberment of Oman into two Sultanates, one in Arabia and the other in East Africa.
Keywords: Zanzibar

Il mausoleo dell’Imàm Aḥmad bin Saʿīd al-Būsaʿīdī e le sue iscrizioni (Al-Rustāq-Sultanato di Oman) - Baldissera, Eros (Quaderni di Studi Arabi, 1998)
Rustāq, ancient capital of Oman, in the eighteenth century was home of Imam Aḥmad bin Saʿīd, the founder of the al-Būsaʿīdī dynasty which has held power since then, when internal strife and a civil war weakened the Yaʿāriba rule and Persians took advantage of the confused situation and occupied Masqaṭ. But Aḥmad bin Saʿīd defeated them and Oman flourished under his government. At his death his son and successor Saʿīd built for him a mausoleum near the famous fort of the city and it was place of pilgrimage until the end of nineteenth century, when it was abondened. After the restauration of 1990 it got again its ancient splendour. With a short historical note and a presentation of the life and work of the Imam, this study presents the sepulcral monument and its inscriptions on five tombstones.
Keywords: Architecture – Oman

Italian studies on Tripolitania tribes - Baldinetti, Anna (The Maghreb Review, 1997)
Keywords: Orientalisme – Italie

ʿAzīz ʿAlī al-Miṣrī: un ufficiale egiziano al fronte libico (1911-13) - Baldinetti, Anna (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 1992)
Keywords: Invasion italienne – Libye

Guellala: A Potter's Village in Tunisia by Sophie Ferchiou - London, Gloria (American Anthropologist, 1990)
Keywords: Recension

Mobile Pastoralists: Development Planning and Social Change in Oman - Robbins, Paul (Economic Geography, 1997)
Keywords: Recension

Documents sur les étudiants maghrébins à l'université al-Azhar au Caire durant les années 1916-1918 - Temimi, Abdeljelil (Revue d'Histoire Maghrébine, 1993)
Keywords: Emigration – Djerba – Egypte

Al-turāth al-ghināʾī al-Jarbī min khilāl al-aghānī al-nisāʾī - Ben Tanfous, Aziza (Cahiers des Arts et Traditions Populaires, 1996)
Keywords: Musique – Djerba

Review : Scholz, F: Muscat, Sultanat Oman, 459 p. - Peppelenbosch, Pim G. N. (GeoJournal, 1991)
Keywords: Recension

The Politics of Participation in the Gulf Cooperation Council States: The Omani Consultative Council - Haj, Abdullah Juma al- (Middle East Journal, 1996)
Keywords: Vie politique – Oman – 1970-2020

Le sultanat d’Oman, une politique étrangère originale - Kutschera, Chris (Les Cahiers de l'Orient, 1990)
Keywords: Vie politique – Oman – 1970-2020

Les relations omano-françaises et les horizons de l'avenir - Rawas, al- (La tribune, 1995)
Keywords: Relations – Oman – France

Kitab al-Siyar, (Kuliyyat al-'Ulūm al-'Insāniyya wa-I-'Ijtimā'iyya. Series 4, vol. 30) by 'Abū al-'Abbās 'Aḥmad ibn Sa'īd al-Shammākhī; Mohammed Hassen - Long, John E. (Middle East Studies Association Bulletin, 1996)
Keywords: Recension

Research Facilities and Document Collections in the Socialist People's Libyan Arab Jamahiriyah - Vandewalle, Dirk (Middle East Studies Association Bulletin, 1994)
Keywords: Bibliothèques – Tripoli

Banū Nabhān in the Omani sources - Nābūda, Ḥasan Muḥammad al- (New Arabian Studies, 1997)

European travelers in Oman and southeast Arabia 1792-1950: a biobibliographical study - Marshall, Brian (New Arabian Studies, 1994)
Keywords: Récits de voyage – Oman

Description of the Johnstone Papers held in the Palace Green Section of the University Library of Durham - Hofstede, Anda (New Arabian Studies, 1997)
Keywords: Archives – Durham

Omani proverbs: problems in translation - Emery, Peter J. (New Arabian Studies, 1997)
Keywords: Littérature – Oman

The pre-metric weights and measures of Oman in the 1970s - Donaldson, W.J. (New Arabian Studies, 1993)

Musandam: an ethno-archaeological appreciation - Costa, Paolo M. (New Arabian Studies, 1993)
Keywords: Archéologie – Oman

Review: La Communication entre Istanbul 1860-1913. Province et métropole by Andreas Tunger-Zanetti - Herzog, Christoph (Die Welt des Islams, 1999)
Keywords: Recension

Omani-Ottoman relations during the reign of Imām Aḥmad b. Saʿīd, 1741-83, in the light of a recently discovered exchange of letters between the Imām and the Ottoman Sultān - Zulfa, Mohammed al- (Arabian Studies, 1990)
Keywords: Vie politique – Oman – 1744-1783

Imam ʿUmar b. al-Haṭṭāb of Oman and Banū Ğabr of Al-Ḥasā - Abu Ezzah, Abdullah M. (Proceedings of the Seminar for Arabian Studies, 1995)
The focal point of this paper is three personalities who were in contact with each other during the last quarter of the ninth century of the Higra (fifteenth century AD). They are the Ibadi Imam 'Umar b. al-Hattäb al-Harüsi of Oman, Agwad b. Zämil al-Gabri, Emir (also King or Sultan) of al-Has, and King Sulaymän b. Sulaymän al-Nabhani of Oman. The sources are mainly Omani, with a few others. It is to be borne in mind that the source material is very scanty, especially for the major point of this paper. It goes without saying that circumstantial evidence has also been used. As is well known, the period extending from the sixth to the ninth centuries (twelfth to fifteenth centuries AD) has been considered a dark age of Arabian Gulf history, but new light has started to dispel the darkness little by little, thanks to the efforts of a few Arab and foreign researchers. It is hoped that this paper will add a modest contribution to the past and future efforts in this direction. Before grappling with the problem of Imam 'Umar b. al-Hattab, we need to illuminate the background of the theatre. This will help us understand and analyse the complex situations.
Keywords: Vie politique – Oman – 15e siècle

The emergence of libraries in the sultanate of Oman - Abdul Karim, Bakri Musa (International Library Review, 1991)
Keywords: Bibliothèques – Oman

Representation of the Cultural Palimpsest: The Case of Manh in Inner Oman - Bandyopadhyay, Soumyen (Traditional Dwellings and Settlements Review, 1996)
Keywords: Urbanisme – Oman

Rethinking Progress: The Case of Oman - Bandyopadhyay, Soumyen (Traditional Dwellings and Settlements Review, 1992)
Keywords: Urbanisme – Oman

نصوص الخوارج في شطط الشواطئ الشاطة - سالم, عفيف (مشارف, 1997)
Keywords: Kharijisme

قراءة جديدة في مواقف الخوارج وفكرهم وأدبهم - اليونس, عبد اللطيف (الثقافة, 1992)
Keywords: Kharijisme

إمارة بني مسالة (إمارة إباضية منسية) - مزهودي, مسعود (العرب, 1998)

الشيعة والخوارج في ميزان المحدثين - العمري, محمد (أبحاث اليرموك, 1991)
Keywords: Kharijisme

شعر الموت عند الخوارج : قراءة جديدة - يوسف, مي أحمد (الموقف الأدبي, 1991)
Keywords: Poésie kharijite

الفتنة الكبرى - الجورشي, صلاح الدين (الإجتهاد, 1991)
Keywords: Fitnah

الأباضية في الفكر السياسي الإسلامي وأثرها في قيام الدول - البريك, ناصر المرشد (الإجتهاد, 1991)

حركة طالب الحق بحضرموت وأثرها في تاريخ اليمن 128 - 130هـ / 746 - 747م - السامرائي, خليل إبراهيم صالح (المؤرخ العربي, 1993)

وسطية أهل السنة في حكم مرتكب الكبيرة بين الخوارج والمرجئة - المعتق, عواد بن عبدالله (مجلة البحوث الإسلامية, 1994)
Keywords: Kharijisme

الإباضية : الطائفة و المذهب - الفاوى, عبدالفتاح أحمد (دراسات عربية وإسلامية, 1994)

الغلو والتطرف في الفرق الإسلامية : الخوارج - مراد, سعيد جمعة (التوحيد, 1995)
Keywords: Kharijisme

الغلو والتطرف في الفرق الإسلامية : الخوارج - مراد, سعيد جمعة (التوحيد, 1997)
Keywords: Kharijisme

القرطبي و موقفه من الخوراج - التكريتي, بهجت كامل عبداللطيف (مجلة الآداب, 1997)
Keywords: Kharijisme

دور البصرة في الحركة الإباضية في القرنين الأول و الثاني الهجريين : دراسة تاريخية في ضوء السير العمانية - سلام, حورية عبده عبد المجيد (مجلة المؤرخ المصري, 1998)

وهب بن منبه - والخوارج - الشويعر, محمد بن سعد (الداعي, 1999)
Keywords: Kharijisme

الخوارج في سجستان حتى ظهور الصفاريين - صديق, أسامة محمد فهمي (المجلة العلمية لكلية الآداب, 1999)
Keywords: Kharijisme

منهج شيخ الإسلام في كشف بدعة الخوارج - سلطان, فتحي عبدالله (الأصالة, 1999)
Keywords: Kharijisme

وجهة نظر أباضية في الفرق الاسلامية - الحديثي, نزار عبد اللطيف (مجلة المجمع العلمى, 1999)

نشأة الخوارج - يعقوب, عبدالكريم; معيطة, أحمد محمود (مجلة جامعة تشرين للبحوث والدراسات العلمية, 1990)
Keywords: Kharijisme

الآفاق الموضوعية والفنية فى شعر الخوارج - عبدالدايم, صابر (مجلة كلية اللغة العربية بالمنوفية, 1990)
Keywords: Poésie kharijite

جمعية التراث بالقرارة و مشروعها الطموح لحماية المخطوطات في منطقة وادي ميزاب (الجزائر) : القسم الأول - عوفي, عبد الكريم (عالم المخطوطات والنوادر, 1999)
Keywords: Manuscrits – Mzab

الامام جابر بن زيد الازدي العماني : حياته ومكانته العلمية - المشهداني, محمد جاسم حمادي (المؤرخ العربي, 1999)

وعاء الزكاة في الفقه الإباضي - الخالدي, محمود عبد المجيد; القضاة, منصور (مجلة كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 1999)
Keywords: Fiqh

أبو خزر الحامي التونسي : المتكلم الإباضي - عامر, ونيس الطاهر (مجلة الهداية, 1998)

أبو خزر الحامي التونسي : المتكلم الإباضي - عامر, ونيس الطاهر (مجلة الهداية, 1998)

الفكر الإباضي و دروه في تأكيد الشخصية العمانية - الشافعي, حسن محمود عبداللطيف (دراسات عربية وإسلامية, 1996)

نظرات فى الفقه الاباضى ورأى آخر ذو فائدة - حسام الدين, محمد (مجلة الأزهر, 1991)
Keywords: Fiqh

نظرات فى الفقه الأباضى نبذة عن المذهب ورجالاته - حسام الدين, محمد (مجلة الأزهر, 1991)
Keywords: Fiqh

نظرات فى الفقه الأباضي : ظاهرة ينبغي رعايتها - 2 - - حسام الدين, محمد (مجلة الأزهر, 1991)
Keywords: Fiqh

الفكر التربوي عند الشيخ الجيطالي (ت 750هـ ) - رجب, مصطفى (المجلة التربوية, 1990)
Keywords: Jayṭālī; Ismāʿīl b. Mūsà (13..-1350)

السياحة بجزيرة جربة و التحولات المجالية الناتجة عنها - المزابي, حسونة (المجلة التونسية للجغرافيا, 1994)
Keywords: Tourisme – Djerba

العلاقات الثقافية بين أباضية جربة وأباضية المغرب الأوسط في القرنين الرابع والخامس للهجرة - مزهودي, مسعود (مجلة العلوم الاجتماعية والإنسانية, 1994)
Keywords: Relations – Djerba – Mzab

العلاقات الثقافية بين اباضية جربة واباضية المغرب الاوسط في القرنين الرابع والخامس للهجرة - مزهودي, مسعود (حوليات الجامعة التونسية, 1995)
Keywords: Relations – Djerba – Mzab

Review of Introduction à l'étude de l'ibadisme et de sa théologie - Cresti, Federico (Oriente Moderno, 1994)
Keywords: Recension

Tourism and national development planning in Tunisia - Gan, Robert; Smith, José (Tourism Management, 1992)
Keywords: Tourisme – Djerba

La pêche dans le gouvernorat de Médenine : modernisation et problèmes d’exploitation des ressources - El Alba, Hammadi (Cahiers du C.E.R.E.S, série geographique, 1995)
Keywords: Pêche – Djerba

Prophetic Parallels in Abu Abd Allah al-Shii's Mission among the Kutama Berbers, 893-910 - Lindsay, James E. (International Journal of Middle East Studies, 1992)

Destination made in heaven (Middle East, 1999)
Keywords: Tourisme – Djerba

Berbers and Blacks: Ibāḍī Slave Traffic in Eighth-Century North Africa - Savage, Elizabeth (The Journal of African History, 1992)
The aim of this article is to illustrate the process whereby certain Berber tribes during the eighth century A.D. substituted slaves from the Bilād al-Sūdān for Berber slaves from North Africa. From the outset, this conversion was influenced strongly, if not instigated, by Ibāḍī merchants until the slave trade became a predominantly Ibāḍī monopoly from the mid-eighth century onwards. The slave trade along the central Sudan route in particular provided the increase in the community's wealth and security, as well as the means for its establishment and expansion as a Muslim sect among diverse Berber tribes and, finally, as the origins for the subsequent, far-flung network of trans-Saharan trade.
Keywords: Esclavage – Afrique du nord

Survival through Alliance: The Establishment of the Ibadiyya - Savage, Elizabeth (Bulletin (British Society for Middle Eastern Studies), 1990)
Keywords: Commerce – Ibadisme; Muhallabides

Tourism and development in Tunisia - Poirier, Robert A. (Annals of Tourism Research, 1995)
Keywords: Tourisme – Djerba

Optat de Milève, Traité contre les donatistes - Alexanderson, Bengt (Augustinianum, 1999)
Keywords: Recension

John C. Wilkinson: The Imamate tradition of Oman. (Cambridge Middle East Library.) xii, 415 pp. Cambridge, etc.: Cambridge University Press, 1987. £35, $59.50. - Burrell, R. M. (Bulletin of the School of Oriental and African Studies, 1990)
Keywords: Recension

The Early Murji'a: Some Notes - Athamina, Khalil (Journal of Semitic Studies, 1990)
Keywords: Kharijisme

A Statement by the Najdiyya Khārijites on the Dispensability of the Imamate - Crone, Patricia (Studia Islamica, 1998)
A translation of Shahrastānī’s account (K. Nihāyat al-Iqdām fī ʿIlm al-Kalām, ed. and transl. A. Guillaume, London 1934, 481 ff. = 152 f.), an attempt to separate its Najdite and Muʿtazilite components, and a general discussion of the doctrines it contains.
Keywords: Kharijisme

Tunger-Zanetti (Andréas) : La communication entre Tunis et Istambul (1860-1913). Province et métropole - Ganiage, Jean (Outre-Mers. Revue d'histoire, 1998)
Keywords: Recension

La Expedicion Epanöla Contra la Isla de Gelves en 1560 - Önalp, Ertuğrul (Journal of The Center for Ottoman Studies Ankara University, 1996)
Keywords: Invasions chrétiennes – Djerba – 1560

Djerba: A Tiro de Piedra - Basabe, Álex (Cambio, 1996)
Keywords: Tourisme – Djerba

Vincenzo Maurizi e David Vatrin: due presenze italiane nell’Oceano Indiano nel 1800 - Nicolini, Beatrice (Africana: Rivista di Studi Extraeuropei, 1999)
Keywords: Zanzibar

Dalla repressione alla politica araba nella colonizzazione agraria della Libia: alcune considerazioni - Cresti, Federico (Africana: Rivista di Studi Extraeuropei, 1999)

Il primo esperimento di colonizzazione demografica in Tripolitania nei documenti d’archivio dell’Azienda Tabacchi Italiani - Cresti, Federico (Africana: Rivista di Studi Extraeuropei, 1997)

La défaite de la flotte espagnole à Jerba en 1510 selon les témoignages italiens: le Diarii de Marin Sanudo, et les lettres de Battistello de Tonsis - Galletti, Mirella (Africana: Rivista di Studi Extraeuropei, 1997)
Keywords: Invasions chrétiennes – Djerba

Un Caso di Pirateria Veneziana: la Cattura della Galea del Bey di Gerba (21 Ottobre 1584) - Fabris, Antonio (Quaderni di Studi Arabi, 1990)
Le document est un article de recherche sur le procès de Gabriele Emo, un commandant vénitien exécuté pour avoir attaqué une galère barbaresque en 1584. Le document explore les détails du procès et la politique de la République de Venise en matière de piraterie et de relations avec l’Empire ottoman, et donne un aperçu de la vie de Ramazan, le père de Mehmet, bey de Djerba.
Keywords: Ottomans – Djerba

Oman: Politics and Development by Ian Skeet. New York: St. Martin's Press, 1992. Pp.195. L35.00 Trade and Empire in Muscat and Zanzibar: Roots of British Domination by M. Reda Bhacker. London: Routledge,1992. Pp.278. L40.00. - Rabi, Uzi (Middle Eastern Studies, 1997)
Keywords: Recension; Vie politique – Oman – 1970-2020

Controcorrente? il Caso Della Comunità Khogia di Zanzibar - Amoretti, Biancamaria Scarcia (Oriente Moderno, 1995)
Keywords: Zanzibar

Le périple de Qalasâdî en Tunisie - Sassi, Jomaa (Revue de l'Institut des Belles Lettres Arabes, 1994)
Keywords: Récits de voyage – Djerba

Jerba and Tripoli: A Comparative Analysis of Two Jewish Communities in the Maghrib - Goldberg, Harvey E. (Journal of Mediterranean Studies, 1994)
Responses to modernity in two North African Jewish centres—Jerba in southern Tunisia and Tripoli in Libya—are compared. The paper first demonstrates the close cultural connections between these communities during the past several centuries. It then shows how Jerba developed as the more active community, in terms of rabbinic culture, in the late 19th century. Next, it points to the main directions the two communities took in response to contact with Europe in the 19th and 20th centuries—sustained resistance on the part of the Jews of Jerba and pragmatic accommodation, while maintaining attachment to tradition, on the part of the Jews of Tripoli. Particular attention will be paid to the way rabbinic culture interacted with wider communal religious culture in each instance. Finally, various explanations for this difference are considered, while citing comparative material from Tunisia and Tripolitania.
Keywords: Judaïsme – Djebel Nefousa; Judaïsme – Djerba

Mishna Tractate Shevi it in the Reading-Tradition of Three Communities by Ktzia Katz - Basser, Herbert W. (Journal of the American Oriental Society, 1995)
Keywords: Recension

The Town of Ghardaïa in M'zab, Algeria: Between Tradition and Modernity - Cataldi, Giancarlo; Abdelhamid, Rasid; Selva, Fabio (Traditional Dwellings and Settlements Review, 1996)
Keywords: Urbanisme – Mzab

Les Djerbiens, des migrants séculaires - Tmarzizet, Kamel (Confluences, 1993)
Keywords: Commerce – Djerba; Emigration – Djerba

Hôtel Cap Djerba, Aghir Djerba - Ben Boubaker, Slah (Architecture méditerranéenne, 1999)
Hotel on Jarbah Island, Tunisia. Architect: Slah Ben Boubaker.
Keywords: Architecture – Djerba

La mission politique de Jérôme Becker auprès de Tippo Tip (1888-1889) - Salmon, Pierre Marcel (Cahiers africains, 1993)
Keywords: Tippo Tip (1837-1905); Zanzibar

Le véritable sens des surnoms africains de Tippo Tip - Bontinck, François (Annales Aequatoria, 1999)
Keywords: Tippo Tip (1837-1905); Zanzibar

An Arabian Princess between Two Worlds. Memoirs, Letters Home, Sequels to the Memoirs, Syrian Customs and Usages. Leiden: E.J. Brill. 1993. Hfl. 250, —/US$ 143.— - Penrad, Jean-Claude (Journal of the Economic and Social History of the Orient, 1995)
Keywords: Recension

Review of Tippo-Tip: un potentat arabe en Afrique centrale au XIXe siècle - Moulin, Léon de Saint (Canadian Journal of African Studies, 1991)
Keywords: Recension; Tippo Tip (1837-1905); Zanzibar

La chefferie en milieu saharien, son fonctionnement et ses rapports avec le pouvoir central de 1830 à 1885 - Romey, Alain (Cahiers de la Méditerranée, 1992)
Keywords: Moeurs et coutumes – Ouargla; Nomadisme – Ouargla; Ouargla – Histoire

Bir et-Uaar Mausoleum (Al-Urban, Djebel Garian) - Abdussaid, Abdulhamid (Libya Antiqua, 1998)
Keywords: Archéologie – Djebel Nefousa

The Umm et-Grib rock-shelter and the exploitation of resources in Jebel Gharbi - Conati Barbaro, Cecilia (Libya Antiqua, 1995)
Keywords: Géologie – Djebel Nefousa

Modern changes of women's life in M'Zab, Algeria - Kowalska-Lewicka, Anna (Ethnologia Polona, 1991)

Développement Régional et Environnement, cas du Gouvernorat de Médenine - Yamoun, Messaoud (Revue Tunisienne de Sciences Sociales, 1993)
Keywords: Développement local – Djerba

Entretien avec M. Tirichine Salah, poète mozabite - Guenoun, Ali (Uttun, 1990)
Keywords: Poésie – Mzab

The Suq al Jum'ah Palaeowadi, an Example of a Plio-Quaternary Palaeo-valley from the Jabal Nafusah, Northwest Libya - Ghellali, S. M.; Anketell, J. M. (Libyan Studies, 1991)
Study of borehole data in the foothill region of the Jabal Nafusah shows that the Suq al Jum'ah palaeowadi, which cuts the jabal east of Gharyan, comprised a major drainage channel which extended in the subsurface far out from the jabal into the southern part of the Jifarah Plain. The channel is filled with sands and gravels. Basalt lava flows, channelled along the valley in outcrop for 36 km, extend for a further 48 km in the subsurface. The palaeowadi was possibly initiated in the Pliocene and appears to have been completely filled and abandoned by the end of the Pleistocene. During Holocene rejuvenation of the drainage system, the Wadi al Majanin developed as the major wadi in the region. It did not, however, excavate the palaeowadi but instead followed a different but roughly parallel northward trend.
Keywords: Archéologie – Djebel Nefousa

Geomorphology and sedimentology in the Ghan and Zargha Wadis and on the Jado Plateau - Giraudi, Carlo (Libya Antiqua, 1995)
Keywords: Géologie – Djebel Nefousa

Geoarchaeology of the Jebel Gharbi Region : outline of the research - Barich, Barbara E.; Giraudi, Carlo; Conati Barbaro, Cecilia; Capezza, Cecilia (Libya Antiqua, 1995)
Keywords: Archéologie – Djebel Nefousa

L’île de Djerba : une architecture de rêve et de tolérance - Mimita, Mohamed Ajmi (Architecture méditerranéenne, 1995)
Keywords: Architecture – Djerba

Fondation du nouveau Ksar du M'zab - Benyoucef, Brahim (Les Cahiers de l'Epau, 1998)
Keywords: Urbanisme – Mzab

Il Berbero di Jerba: Rapporto Preliminare - Brugnatelli, Vermondo (Incontri Linguistici, 1998)
Keywords: Linguistique

La fin du berbère à Djerba : repères sociolinguistiques et implications sur le système tripolaire de Tunisie - Manzano, Francis (Cahiers de sociolinguistique, 1999)
Keywords: Linguistique

Zum Arabischen Von Djerba (Tunesien) II : Texte - Behnstedt, Peter (Zeitschrift Für Arabische Linguistik, 1999)
Keywords: Linguistique – Djerba

Zum Arabischen Von Djerba (Tunesien) - Behnstedt, Peter (Zeitschrift Für Arabische Linguistik, 1998)
On pp. 80-81 a name list of Ibāḍī families. P. 82: a map indicating the regions where mainly Ibāḍīs or Mālikīs live. P. 83: a map with percentages of Berber speakers and bilinguals (Berber and Arabic
Keywords: Linguistique – Djerba

Apotropäische Zeichen und Gegenstände an Bauwerken auf Djerba - Fosshag, Bengt (Baessler-Archiv, 1993)
Keywords: Architecture – Djerba

Emile Masqueray au Mzab: à la recherche de livres ibâdites - Ould-Braham, Ouahmi (Études et Documents Berbères, 1992)
Keywords: Orientalisme – France

The social representation of historic time in Maghrib culture - Najar, Sihem (The Journal of North African Studies, 1997)
The alimentary rituals of daily life are a means of reinforcing its sense of the eternal present. This concept of the tragic is to be contrasted with the links between present and future as reflected in the religious visions where contemporary taboos become the permissiveness of Paradise. The argument is illustrated by the role played by a specific dish, m'hammas, in defining rites of passage, both those of marriage and widowhood.
Keywords: Alimentation – Djerba

De la transculturalité des figures ludiques - Gana, Kamel (Revue de l'Institut des Belles Lettres Arabes, 1991)
jeux
Keywords: Jeux – Djerba

Djerba ou l’importance des femmes dans un système agnatique - Vernier, Bernard (Regards Sociologiques, 1998)
Keywords: Moeurs et coutumes – Djerba

Une tradition musicale de transe afro-maghrébine Stambali - Gouja, Zouhair (Cahiers des Arts et Traditions Populaires, 1996)
Keywords: Musique – Djerba

A Midrash about the Patriarch Abraham in the Passover Haggadah of Djerba / מדרש על אברהם אבינו בהגדה של פסח של יהודי ג'רבה - אילן, נחם; Ilan, Nahem (Sefunot: Studies and Sources on the History of the Jewish Communities in the East, 1993)
The Passover Haggadah is a unique ritual text because it is used in a religious ceremony celebrated at home with the participation of the entire family. The children are at the center of the event. Since the text is primarily Hebrew, whoever led the seder in various Jewish communities felt compelled to translate the text to the language spoken by Jews in that community so that the content of the Haggadah would be clear to all the participants and their children enabling them to fulfill the commandment 'And you will tell your son.' For this reason we find Haggadot in many Jewish languages. The Haggadah of the Jews of Djerba includes a passage in Arabic, which, according to the author of this article, does not appear in any other version. This Haggadah adds, after the passage: 'At first our fathers were idolators' an adaptation of three midrashic traditions on the Patriarch Abraham and how he came to acknowledge and believe in the one God even though he lived in a totally idolatrous environment. The article surveys the various Djerban traditions in which the passage appears, councluding that this text came to be included in the Djerban custom no later than the early eighteenth century. The text is presented revealing the variations in the way it was written, though changes of content were few and insignificant. Obviously the text is written in a very vulgar form of Judeo-Arabic as befits its function and purpose. A literary analysis of the text reveals how the midrashim were adapted to the seder service. Details that were irrelevant to the educational purpose of the seder were omitted and others were altered in order to fit better into the story of the Exodus from Egypt. In conclusion, the text is a witness to the dynamic character of the seder among the Jews of Djerba and a unique expression of the Passover Haggadah tradition in Djerba. In addition to its special context it may be added to the midrashic traditions concerning the Patriarch Abraham adding a unique Djerban dimension to them.
Keywords: Judaïsme – Djerba

Near the Jerba Beach: Tunisian Jews, an Anthropologist, and Other Visitors - Deshen, Shlomo (Jewish Social Studies, 1997)
Keywords: Judaïsme – Djerba

Relations vestimentaires entre Jerba et Tripoli - Ben Tanfous, Aziza (Cahiers des Arts et Traditions Populaires, 1996)
Keywords: Artisanat – Djerba

Données nouvelles sur le Jurassique du Golfe de Gabes autour de l’île de Djerba (Tunisie) - Mzoughi, Moncef; Dufaure, P.; Peybernes, B. (Comptes rendus de l’Académie des sciences, 1992)
Keywords: Géologie – Djerba

Sur la richesse des côtes tunisiennes en industrie lithiques préhistorique - Oueslati, Ameur (Revue tunisienne de géographie, 1995)
Keywords: Géologie – Djerba

The evolution of low Tunisian coasts in historical times: From progradation to erosion and salinization - Oueslati, Ameur (Quaternary International, 1995)
Keywords: Géologie – Djerba

Les ambiances thermiques à l’île de Djerba (Tunisie) - Hénia, L.; Alouane, T. (Publications de l'Association internationale de climatologie, 1999)
L'année est découpée en deux saisons : une longue saison douce et confortable, à priori favorable à l'organisme humain mais caractérisée par une importante variabilité interhoraire aussi bien qu'inter-journalière ; et une courte saison chaude, torride lorsque les vents soufflent du Sahara, période propice aux activités balnéaires mais comportant des risques non négligeables pour la santé
Keywords: Climat – Djerba

La dynamique des commerces maghrébins et asiatiques et les perspectives du marché intérieur européen - Simon, Gildas; Ma Mung, Emmanuel (Annales de géographie, 1990)
Le développement du commerce tenu par les étrangers est lié à la crise économique et aux mutations de l'appareil commercial. Il est le fait de commerçants issus de groupes régionaux spécifiques ayant acquis dans leur pays d'origine une solide tradition commerçante et migratoire. La puissance des structures communautaires explique la forte capacité d'autofinancement de ces groupes et donne lieu à la mise en place de circuits économiques ethniques. Le lieu communautaire se retrouve dans les formes d'exploitation et à travers le recrutement de la main-d'œuvre. L'augmentation du nombre et de la taille des établissements et la diversification de leurs activités, la constitution de réseaux transnationaux et les ressources financières et humaines des commerçants maghrébins et asiatiques donnent à penser que ces entrepreneurs ethniques ne seront pas les derniers venus dans le grand marché de 1993.
Keywords: Emigration – Djerba – France

L'émigration dans la Tunisie du Sud-Est et ses conséquences sur la région - Mzabi, Hassouna (Cahiers de la Méditerranée, 1994)
Keywords: Démographie – Djerba

Le Corbusier et le mirage de l'Orient. L'influence supposée de l'Algérie sur son œuvre architecturale - Gerber, Alex (Revue des mondes musulmans et de la Méditerranée, 1994)
Keywords: Architecture – Mzab

Ports de pêche et dynamique littorale à Djerba et Zarzis - Bourgou, Mongi (Cahiers du C.E.R.E.S, série geographique, 1995)
Keywords: Pêche – Djerba

Milieu littoral et aménagement : le cas du littoral nord oriental de la presqu’île de Zarzis - Bourgou, Mongi (Revue tunisienne de géographie, 1995)
Keywords: Littoraux – Djerba

L’impact des mutations socio-économiques récentes à Jerba, sur le milieu naturel - Bourgou, Mongi (Revue tunisienne de géographie, 1993)

Post-Mortem Onshore Transportation of Epiphytic Foraminifera: Recent Example from the Tunisian Coastline - Davaud, Eric; Septfontaine, Michel (Journal of Sedimentary Research, 1995)
The barrier island system that connects Jerba Island to the Tunisian coastline is composed mainly of carbonate bioclastic sands. Well-preserved tests of dead epiphytic foraminifera are abundant on the foreshore and backshore, but they are scattered and poorly preserved on the shoreface, where very fine sand-size eolian quartz, peloids, and broken bioclasts are the main components. The reason for this paradoxical pattern is that most epiphytic foraminifera are very easily removed as suspended load by storm-generated currents and concentrated on beaches, washover fans, and small eolian dunes, kilometers avay from their original life environment. Similar bioaccumulations are common in the fossil record and have often been interpreted incorrectly as prolific biocoenoses.
Keywords: Littoraux – Djerba

La protection côtière intégrée dans l’île de Djerba en Tunisie : réalités et perspectives - Baouendi, Abdelkader (CIESM Workshop, 1999)

Evaporite, carbonate, and siliciclastic transitions in the Jurassic sequences of southeastern Tunisia - Ben Ismail, Mohamed Hédi; M'Rabet, Ali (Sedimentary Geology, 1990)
Evaporite, carbonate and siliciclastic transitions occur within the Jurassic deposits of southeastern Tunisia. These facies are grouped into four major transgressive-regressive sequences corresponding to various environments of deposition. The latter include sabkha, subaqueous evaporite basin, carbonate tidal flats to shallow marine platform, bioherms and mixed siliciclastic ramp. Rapid lateral and vertical variations in thicknesses and facies are controlled by tectonic, climatic and eustatic factors. East-west and NW-SE fault systems generated a down-faulted graben (Tataouine basin) bordered by two uplifted horsts (Tebaga Mole and Libyan Craton) and have acted as an evaporite depocenter or as a siliciclastic trap. Eustatic-related transgressions occurring during Late Lias, Bajocian, Early/Middle Callovian, and probable Upper Callovian-Oxfordian have led to opening and/or deepening of the marine basin accompanied by carbonate sedimentation rapidly replacing evaporite or siliciclastic deposition. This Jurassic example not only confirms that tectonics and, to a lesser extent, climate largely controlled evaporite, carbonate, and siliciclastic transitions; it also demonstrates that sea-level changes may be another factor controlling such transitions in these ancient deposits.
Keywords: Géologie – Djebel Nefousa

Taxonomy of Saldula: revised genus and species group definitions, and a new species of the pallipes group from Tunisia (Heteroptera: Saldidae) - Polhemus, John T.; Lindskog, Per (Insect Systematics & Evolution, 1992)
A revised diagnosis of the genus Saldula Van Duzee based upon synapomorphic characters of male genitalia and hemelytral pigmentation patterns is given. According to this concept ca. 55% of the species World-wide currently assigned to Saldula will have to be transferred to other genera. Several new characters are employed in the definition of species and species groups. The species attributable to the pallipes species group are listed and supplemented by a brief overview of the taxonomic relationships of the Old World species. Saldula luteola sp. n. is described from coastal salt marshes on the Island of Djerba, Tunisia. It mainly appears in extremely depigmented morphs unparalleled elsewhere in the Saldidae and likely constitutes a sister-species of S. sardoa Filippi. The conspicuous intraspecific variation in body size and hemelytral pigmentation in S. palustris (Douglas), the closest relative of the former species, is depicted and briefly discussed. The descriptive accounts are accompanied by numerous photographic illustrations of somatic and genital characters.
Keywords: Entomologie – Djerba

Etude paléo-écologique (pollen et macrorestes) d'un dépôt tourbeux dans l'île de Djerba, Tunisie méridionale. - Damblon, Freddy; Vanden Berghen, Constant (Palynosciences, 1993)
Keywords: Botanique – Djerba

Les bijoux de Djerba - Gargouri-Sethom, Samira (Cahiers des Arts et Traditions Populaires, 1990)
Keywords: Artisanat – Djerba

L'impact de la colonisation sur les échanges commerciaux de Djerba - Ben Hamida, Abdessalem (Cahiers de la Méditerranée, 1994)
Keywords: Commerce – Djerba – 1881-1956

Gightis municipe latin d'Hadrien ? - Chastagnol, André (Bulletin archéologique du Comité des travaux historiques. (B) Afrique du Nord, 1995)
Keywords: Archéologie – Djerba

Le Sahel et l’île de Djerba, les caractéristiques de l’architecture funéraire punique - Ben Younes, Habib (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 1996)
Keywords: Antiquité; Archéologie – Djerba

Le littoral de la Tunisie dans l'Antiquité : cinq ans de recherches géo- archéologiques - Paskoff, Roland; Slim, Hédi; Trousset, Pol (Comptes-rendus des séances de l'année, 1991)
Keywords: Antiquité; Archéologie – Djerba

Ehrenmonumente des L. Minicius Natalis in Rom und Africa - Erkelenz, Dirk (Zeitschrift für Papyrologie und Epigraphik, 1998)
Keywords: Antiquité; Archéologie – Djerba

Sur les finances municipales en Afrique romaine sous le Haut-Empire - Beschaouch, Azedine (Comptes-rendus des séances de l'année, 1999)
La redécouverte de l'inscription « de Meninx » (CIL VIII 11058)
Keywords: Antiquité; Archéologie – Djerba

Un ensemble méconnu : Les piliers sculptés de Méninx - Baratte, François (Karthago, 1995)
L’hommage rendu à un savant dont les travaux ont été consacrés avec tant de prédilection à l’Afrique comme aux représentations du triomphe dans l’art romain ne pouvait être une meilleure occasion d’attirer de nouveau l’attention sur un monument connu depuis plus d’un siècle, mais qui n’a pourtant jamais suscité l’intérêt qu’il mérite. Le cadre limité qui nous est imparti ne nous permet d’ailleurs de donner ici qu’une étude préliminaire d’un ensemble qui réclamerait en fait une publication plus détaillée.
Keywords: Archéologie – Djerba

La nécropole lybico-punique de Ghizene (Djerba-Tunisie) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 1995)
Keywords: Antiquité; Archéologie – Djerba

Note préliminaire sur deux tombes phénico-puniques à Agga au Nord-Ouest de Djerba - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 1995)
Keywords: Antiquité; Archéologie – Djerba

Les Hypogées de Meninx (Jerba) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 1993)
Keywords: Antiquité; Archéologie – Djerba

Les haouanet d’Oulad Amor (Trifa) : Témoin protohistorique dans l’île de Jerba (Tunisie) - Akkari-Weriemmi, Jenina (Préhistoire, Anthropologie Méditerranéennes, 1992)
Keywords: Antiquité; Archéologie – Djerba

تجار جربة أثناء الحكم الفرنسي المباشر لتونس (1881 - 1956) - جلاب, الهادي (مجلة روافد, 1994)
Keywords: Emigration – Djerba – Tunis

L'état des recherches tunisiennes sur la presse (1881-1986): une approche globale - Hassan, Mustapha (Revue Tunisienne de Communication, 1994)
Keywords: الجادوي، سليمان (1871-1951)

Jeux traditionnels de Jerba (Tunisie) - Akkari-Weriemmi, Jenina (Revue de l'Institut des Belles Lettres Arabes, 1990)
Keywords: Jeux – Djerba

Migrations intérieures dans la Tunisie du XIXe siècle le cas des insulaires Jerbiens - Regaya, Mourad (Revue de l'Institut des Belles Lettres Arabes, 1993)
Les flux migratoires ont existé, en Tunisie depuis l’aube des temps, mais leur étude et leur quantification ne devinrent possibles qu’avec l’ère des recensements démographiques. En fait, ceux-ci n’ont existé que dans la deuxième moitié du XIXe siècle. Leur étude a pu être abordée grâce à l’existence des registres fiscaux de l’ancienne administration beylicale.
Based on a decree of poll tax, dated July 1856, in the Tunisian archives of Dar El Bey, concerning Jerba. In appendix this document provides an exhaustive list of Jerbans residing outside of Jerba.
Keywords: Emigration – Djerba – Tunis